Carbon nanotube dispersion liquid, and resin composition, conductive film, composite slurry, electrode, and nonaqueous electrolyte secondary battery using same

By developing a dispersion of bundled carbon nanotubes with specific proportions and shapes and applying them in batteries, the problem of reducing conductivity of carbon nanotube dispersions in the prior art is solved, and the excellent cycle characteristics and film thickness of the battery are achieved. Maintainability.

CN119487654APending Publication Date: 2025-02-18아티엔스가부시키가이샤
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202380051653.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-26
Filing Date
2023-09-26
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, it is difficult to obtain carbon nanotubes with a bale shape stably, especially in batteries using silicon as the negative electrode active material, and it is difficult to obtain excellent cycle characteristics.

Method used

A carbon nanotube dispersion liquid was developed, including bundled carbon nanotubes with an average diameter of 3 nm to 30 nm and a solvent, ensuring that the ratio of bundled carbon nanotubes with an outer diameter of 50 nm to 5 μm and a fiber length of 1 μm to 100 μm is 0.2 % or more, and a dispersant is added to improve the resistivity of the composite layer and its follow-up to expansion or shrinkage.

Benefits of technology

By using the carbon nanotube dispersion, the strength and peel strength of the electrode film are improved, and the film thickness can be maintained under high stress, which significantly improves the circulation characteristics of the lithium-ion secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005226476490000251
    Figure BDA0005226476490000251
  • Figure HDA0005226476500000011
    Figure HDA0005226476500000011
Patent Text Reader

Abstract

In the present disclosure, provided is a carbon nanotube dispersion liquid which contains a solvent and bundle-shaped carbon nanotubes that use carbon nanotubes having an average diameter of 3-30 nm, and in which the number of carbon nanotubes having an outer diameter of 10 nm or more contained in the carbon nanotube dispersion liquid is less than or equal to 1% by weight, and the number of carbon nanotubes having an outer diameter of 10 nm or more contained in the carbon nanotube dispersion liquid is less than or equal to 1% by weight. The ratio of the number of bundle-shaped carbon nanotubes having an outer diameter of 50 nm to 5 [mu] m and a fiber length of 1 [mu] m to 100 [mu] m is 0.2% or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a carbon nanotube dispersion liquid containing carbon nanotubes in a bundle shape. More specifically, it relates to a resin composition containing the carbon nanotube dispersion liquid and a resin, a composite material slurry containing the carbon nanotube dispersion liquid, a resin and an active material, a conductive film and an electrode film formed of these into a film shape, and a non-aqueous electrolyte secondary battery including an electrode film and an electrolyte. Background Art

[0002] In recent years, the development of electronics has been very significant. For conductive materials used in various electronic devices or batteries, the products are required to be small, lightweight, low-cost, and have a long life in various usage environments. In addition, various conductive carbon materials with low volume resistivity such as graphite and carbon nanotubes have been studied so far.

[0003] On the other hand, when conductive materials are used in various electronic devices or batteries, a dispersion obtained by dispersing the conductive materials in a solvent is often used. However, there is a major problem of reduced properties such as reduced conductivity due to dispersion. Therefore, it is very important to prepare a dispersion that can obtain desired properties.

[0004] If lithium-ion secondary batteries are cited as an example, carbon materials represented by graphite with a low potential close to lithium and a large charge and discharge capacity per unit mass are used as negative electrode materials used in lithium-ion secondary batteries. However, these electrode materials have been used until the charge and discharge capacity per mass is close to the theoretical value, and the energy density per mass of the battery is close to the limit. Therefore, in order to improve the utilization rate as an electrode, attempts are being made to reduce conductive additives or adhesives that do not contribute to the discharge capacity.

[0005] As conductive additives, carbon black, Ketjen Black, graphene, fine carbon materials, etc. are used, and in particular, carbon nanotubes, which are a type of fine carbon fiber, are mostly used. For example, Patent Documents 1 to 3 disclose that by adding carbon nanotubes to graphite or silicon as negative electrode active materials, the electrode resistance value is reduced, the internal resistance of the battery is improved, the strength of the electrode is increased, and the expansion and contraction of the electrode is improved, thereby improving the cycle life of the lithium ion secondary battery.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Laid-Open No. 4-155776

[0009] Patent Document 2: Japanese Patent Laid-Open No. 4-237971

[0010] Patent Document 3: Japanese Patent Application Publication No. 2004-178922

[0011] Patent Document 4: Japanese Patent Publication No. 2018-534731

[0012] Patent Document 5: Japanese Patent Publication No. 2018-534747

[0013] However, it is difficult to stably obtain carbon nanotubes having a bundle shape as disclosed in Patent Documents 4 and 5, and it is difficult to obtain excellent cycle characteristics, particularly in a battery using silicon as a negative electrode active material. Summary of the invention

[0014] Problems to be solved by the invention

[0015] The present disclosure aims to provide a carbon nanotube dispersion having excellent cycle characteristics when used as a battery, and a resin composition, a conductive film, a composite material slurry, an electrode, and a non-aqueous electrolyte secondary battery using the dispersion.

[0016] Technical means of solving problems

[0017] A carbon nanotube dispersion according to one embodiment of the present invention comprises bundled carbon nanotubes using carbon nanotubes having an average diameter of 3 nm to 30 nm and a solvent, wherein the carbon nanotube dispersion is characterized in that, based on the number of carbon nanotubes having an outer diameter of 10 nm or more contained in the carbon nanotube dispersion, the proportion of bundled carbon nanotubes having an outer diameter of 50 nm to 5 μm and a fiber length of 1 μm to 100 μm is greater than 0.2%.

[0018] The carbon nanotube dispersion of one embodiment of the present invention is characterized in that the average aspect ratio of the bundled carbon nanotubes having an outer diameter of 50 nm to 5 μm and a fiber length of 1 μm to 100 μm is 5 to 100.

[0019] The carbon nanotube dispersion according to an embodiment of the present invention is characterized in that it further comprises a dispersant.

[0020] A conductive film according to an embodiment of the present invention is characterized in that it is a coating film of the carbon nanotube dispersion liquid.

[0021] A carbon nanotube resin composition according to an embodiment of the present invention is characterized by comprising: the carbon nanotube dispersion and a binder.

[0022] The composite material slurry according to an embodiment of the present invention is characterized by comprising: the carbon nanotube resin composition and an active substance.

[0023] An electrode film according to an embodiment of the present invention is characterized in that it is a coating film of the composite material slurry.

[0024] A nonaqueous electrolyte secondary battery according to an embodiment of the present invention includes a positive electrode, a negative electrode, and an electrolyte. The nonaqueous electrolyte secondary battery is characterized in that at least one of the positive electrode or the negative electrode includes the electrode film.

[0025] Effects of the Invention

[0026] The present disclosure can provide a carbon nanotube dispersion having excellent cycle characteristics when used as a battery, and a resin composition, a conductive film, a composite material slurry, an electrode, and a non-aqueous electrolyte secondary battery using the dispersion. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] [ Figure 1 ] Figure 1 This is a diagram obtained by processing an image obtained by observing the carbon nanotube dispersion described in Example 1 at a magnification of 20,000 times using a scanning electron microscope using image analysis software (WINROOF2015: manufactured by Mitani Shoji Co., Ltd.). DETAILED DESCRIPTION

[0028] <Carbon Nanotube Dispersion Liquid>

[0029] The carbon nanotube dispersion disclosed herein is characterized in that it contains bundled carbon nanotubes using carbon nanotubes having an average diameter of 3 nm to 30 nm and a solvent, and, based on the number of carbon nanotubes having an outer diameter of 10 nm or more contained in the carbon nanotube dispersion, the proportion of bundled carbon nanotubes (X) having an outer diameter of 50 nm to 5 μm and a fiber length of 1 μm to 100 μm is greater than 0.2%.

[0030] By containing a certain amount of bundled carbon nanotubes (X) having such a prescribed shape, not only the resistivity of the composite material layer is reduced, but also the followability to expansion or contraction is improved. As a result, the electrode film is toughened and the peel strength is improved. Moreover, during charging and discharging with a large stress, the stability of the coating film is increased and the film thickness can be maintained. In addition, excellent cycle characteristics can be exerted.

[0031] Hereinafter, the carbon nanotube dispersion, resin composition, conductive film, composite material slurry, electrode, and non-aqueous electrolyte secondary battery disclosed in the present invention will be described in detail. In this specification, carbon nanotubes (carbon nanotubes) are sometimes referred to as CNTs.

[0032] <Bundled carbon nanotubes>

[0033] The bundled carbon nanotubes contained in the carbon nanotube dispersion of the present disclosure are carbon nanotubes having a bundle shape formed by using carbon nanotubes having an average diameter of 3nm to 30nm. The so-called bundled carbon nanotubes refer to a bundle (bundle) formed by arranging or arranging a plurality of carbon nanotubes side by side in a certain direction, and the so-called outer diameter and fiber length refer to the outer diameter (minor diameter) and fiber length (major diameter) of the bundle (bundle).

[0034] The dispersion of the present disclosure contains a predetermined amount of bundled carbon nanotubes (X) having a predetermined outer diameter and fiber length.

[0035] The outer diameter and fiber length of the bundled carbon nanotubes in the dispersion can be determined by observing a sample obtained by drying the dispersion diluted as necessary using a scanning electron microscope (SEM) so that the carbon nanotubes do not overlap and their sizes can be easily distinguished, and performing image analysis.

[0036] In addition, when carbon nanotubes aggregate due to dilution of the carbon nanotube dispersion, an additive such as a dispersant or a water-soluble solvent may be added in an amount of 0.01% to 2% by mass relative to the solid content of the carbon nanotubes, and the mixture may be uniformly mixed using ultrasound, and then diluted 1000 times. In addition, regarding the sample for SEM observation obtained by drying the dispersion, specifically, the diluted solution of the carbon nanotube dispersion may be applied to a mica substrate, and after drying the solvent in an oven, the substrate surface on the coated side may be sputtered with platinum.

[0037] Specifically, in order to more appropriately observe the carbon nanotubes using a scanning electron microscope, the outer diameter (minor diameter), fiber length (major diameter), and area of ​​each particle of the carbon nanotube photographed at a magnification of 10,000 times or 20,000 times were measured using image analysis software (WINROOF2015: manufactured by Mitani Shoji Co., Ltd.). In addition, the shape of the bundled carbon nanotubes is amorphous, and in this specification, since the values ​​of the inner and outer diameters of one carbon nanotube have a range, the value obtained by dividing the area value by the fiber length (major diameter) is used as the outer diameter.

[0038] Next, 1000 carbon nanotube particles having an outer diameter of 10 nm or more determined in the above manner are randomly selected, and among the 1000 carbon nanotube particles, particles having an outer diameter of 50 nm to 5 μm and a fiber length of 1 μm to 100 μm are determined. The number A is counted, and the ratio (%) of the number of bundled carbon nanotubes (X) is calculated using the following formula.

[0039] (Formula) Ratio of the number of bundled carbon nanotubes (X) = A / 1000×100

[0040] The ratio of the number of bundled carbon nanotubes (X) is preferably 0.5% or more, preferably 20% or less, more preferably 10% or less, and further preferably 5% or less. For example, the ratio may be 0.5% to 20%.

[0041] Particularly, from the viewpoint of cycle characteristics and film thickness change rate, 0.5% to 20% is preferable.

[0042] In this specification, the values ​​obtained by averaging the outer diameter and fiber length of particles having an outer diameter of 50 nm to 5 μm and a fiber length of 1 μm to 100 μm determined in the above manner are referred to as average outer diameter and average fiber length. In addition, the ratio of the average outer diameter to the average fiber length is referred to as average aspect ratio.

[0043] The average outer diameter of the bundled carbon nanotubes having an outer diameter of 50 nm to 5 μm and a fiber length of 1 μm to 100 μm in the dispersion of the present disclosure is preferably 50 nm to 1 μm, more preferably 50 nm to 500 nm.

[0044] The average fiber length is preferably 1 μm to 50 μm, more preferably 1 μm to 10 μm. The average aspect ratio is preferably 5 to 200, more preferably 10 to 150.

[0045] The carbon nanotube dispersion of the present disclosure may further contain bundled carbon nanotubes (Y) having an outer diameter of 10 nm or more and less than 50 nm and a fiber length of 1 μm to 5 μm. Such bundled carbon nanotubes (Y) mainly play the role of forming a network of conductive paths to improve cycle characteristics.

[0046] The ratio of the bundled carbon nanotubes (Y) is preferably 10% to 60% based on the number of carbon nanotubes having an outer diameter of 10 nm or more and a fiber length of 0.2 μm or more contained in the carbon nanotube dispersion from the viewpoint of improving cycle characteristics.

[0047] The calculation method of the number ratio is described below. Using a scanning electron microscope, each particle of the carbon nanotubes was photographed at a magnification of 5,000 times the fiber length of the carbon nanotubes, and the outer diameter (minor diameter), fiber length (major diameter), and area were measured using image analysis software (WINROOF2015: manufactured by Mitani Shoji Co., Ltd.). In addition, the shape of the bundled carbon nanotubes is amorphous. In this specification, since the values ​​of the inner and outer diameters of a carbon nanotube have a range, the value obtained by dividing the area value by the fiber length (major diameter) is used as the outer diameter.

[0048] Next, 1000 carbon nanotube particles having an outer diameter of greater than 10 nm and a fiber length of greater than 0.2 μm determined in the above manner are randomly selected. Among the 1000 carbon nanotube particles, particles having an outer diameter of greater than 10 nm and less than 50 nm and a fiber length of 1 μm to 5 μm are determined, the number B is counted, and the proportion (%) of the number of bundled carbon nanotubes (Y) is calculated using the following formula.

[0049] (Formula) Ratio of the number of bundled carbon nanotubes (Y) (%) = B / 1000×100

[0050] From the viewpoint of cycle characteristics, the ratio of the number of bundled carbon nanotubes (Y) is preferably 10% or more, more preferably 20% or more, and is preferably 60% or less, more preferably 35% or less.

[0051] The carbon nanotube dispersion of the present disclosure may further contain bundled carbon nanotubes (Z) having an outer diameter of 10 nm or more and less than 50 nm and a fiber length of 0.2 μm or more and less than 1 μm. It is speculated that such bundled carbon nanotubes (Z) enter the vicinity of the surface of the active material described later or the gap of the conductive network, thereby not only reducing the volume resistivity but also helping to improve the cycle characteristics.

[0052] The ratio of the bundled carbon nanotubes (Z) is preferably 50% to 80% based on the number of carbon nanotubes having an outer diameter of 10 nm or more and a fiber length of 0.2 μm or more contained in the carbon nanotube dispersion from the viewpoint of improving cycle characteristics.

[0053] The calculation method of the number ratio is described below. Using a scanning electron microscope, each particle of the carbon nanotubes was photographed at a magnification of 5,000 times the fiber length of the carbon nanotubes, and the outer diameter (minor diameter), fiber length (major diameter), and area were measured using image analysis software (WINROOF2015: manufactured by Mitani Shoji Co., Ltd.). In addition, the shape of the bundled carbon nanotubes is amorphous. In this specification, since the values ​​of the inner and outer diameters of a carbon nanotube have a range, the value obtained by dividing the area value by the fiber length (major diameter) is used as the outer diameter.

[0054] Next, observe the carbon nanotube particles with an outer diameter of greater than 10 nm and a fiber length of greater than 0.2 μm obtained in the above manner, and randomly select 1000 of them. Among the 1000 carbon nanotube particles, determine the particles with an outer diameter of greater than 10 nm and less than 50 nm and a fiber length of greater than 0.2 μm and less than 1 μm. Count the number C of particles and calculate the ratio (%) of the number of bundled carbon nanotubes (Z) using the following formula.

[0055] (Formula) Ratio of the number of bundled carbon nanotubes (Z) (%) = C / 1000×100

[0056] From the viewpoint of volume resistivity, the ratio of the number of bundled carbon nanotubes (Z) is preferably 30% or more, more preferably 50% or more, and is preferably 90% or less, more preferably 70% or less.

[0057] The dispersion disclosed in the present invention contains bundled carbon nanotubes (X), bundled carbon nanotubes (Y), and bundled carbon nanotubes (Z) having different outer diameters and fiber lengths in an optimal balance, thereby improving the cycle characteristics and film thickness maintenance. From the viewpoint of cycle characteristics and film thickness maintenance, the ratio of the number of bundled carbon nanotubes (Y) to the number of bundled carbon nanotubes (Z) (ratio of the number of (Y) / ratio of the number of (Z)) is preferably greater than 0.1, more preferably greater than 0.3. In addition, it is preferably less than 1.3, more preferably less than 1.0, and further preferably less than 0.6. For example, the ratio may be 0.3 to 0.6.

[0058] The dispersion containing such bundled carbon nanotubes can be obtained, for example, by promoting the interaction between carbon nanotubes and then dispersing them in a solvent (also referred to as a dispersion solvent). In order to promote the interaction between carbon nanotubes, it is preferred to apply shear (force) or impact (force) to the carbon nanotubes and to perform wet mixing using a solvent (also referred to as a treatment solvent), but it is not limited to these.

[0059] As an example of this, there can be cited: wet mixing in the presence of the most suitable treatment solvent using the most suitable device by applying shear (force) or impact (force) in a manner to cause selective agglomeration between carbon nanotubes with an average diameter of 3nm to 30nm, followed by calcination, and dispersing the treated carbon nanotubes obtained in this way in the presence of a dispersing solvent. By dispersing the treated carbon nanotubes obtained in the above manner, a dispersion containing a specified amount of bundled carbon nanotubes (X) having a specified shape as specified in the present disclosure can be obtained.

[0060] [Raw material carbon nanotubes]

[0061] The raw material carbon nanotubes used in the formation of bundled carbon nanotubes refer to carbon nanotubes that are the constituent units of bundled carbon nanotubes (bundles). The raw material carbon nanotubes are important in that their average diameter is 3nm to 30nm. Carbon nanotubes of this average diameter are not only cheap and easy to obtain, but also by using carbon nanotubes of this average diameter, long bundled carbon nanotubes with excellent flexibility can be formed, which can exert excellent cycle characteristics.

[0062] The diameter of the raw carbon nanotubes can be measured using a transmission electron microscope (TEM), for example, at a magnification of 5 million times. The average diameter of the raw carbon nanotubes is the average value of the diameters of any 10 locations in the carbon nanotube fiber. The average diameter of the raw carbon nanotubes is preferably 5 nm to 20 nm.

[0063] The carbon nanotube has a shape in which a flat graphite is wound into a cylindrical shape, and the multilayer carbon nanotube has a structure in which two or more layers of graphite are wound. In addition, the sidewall of the carbon nanotube may not be a graphite structure. For example, a carbon nanotube having a sidewall having an amorphous structure may also be used as the carbon nanotube. In addition, these carbon nanotubes may also be carbon nanotubes in which a plurality of layers of carbon nanotubes are mixed.

[0064] The raw material carbon nanotubes used in the present disclosure are not particularly limited as long as the average diameter is 3 nm to 30 nm, and the number of layers is preferably 2 or more, more preferably 3 or more, and preferably 30 or less, more preferably 20 or less, and even more preferably 10 or less.

[0065] The shape of the raw carbon nanotubes is not limited, and various shapes including needle-shaped, cylindrical, fishbone (fishbone or cup stacking type), and coil-shaped can be used. In addition, it can also be a secondary aggregate in the form of a plate or a platelet obtained by dry-treating cylindrical carbon nanotubes. The shape of the raw carbon nanotubes used in the present disclosure is preferably needle-shaped or cylindrical. The carbon nanotubes can be a single shape or a combination of two or more shapes.

[0066] Examples of the raw material carbon nanotubes include graphite whiskers, filamentous carbon, graphite fibers, ultrafine carbon tubes, carbon tubes, carbon fibrils, carbon microtubes, and carbon nanofibers, but are not limited thereto. Carbon nanotubes may have any of these forms alone or in combination of two or more forms.

[0067] The Brunauer-Emmett-Teller (BET) specific surface area of ​​the raw carbon nanotubes is preferably 10 m 2 / g~1500m 2 / g, more preferably 150m 2 / g~800m 2 / g, and more preferably 200m 2 / g~700m 2 / g.

[0068] The volume resistivity of the raw material carbon nanotubes is preferably 1.0×10 -2 Ω·cm or less, more preferably 5.0×10 -3Ω·cm or less, more preferably 3.0×10 -3 The volume resistivity of the carbon nanotubes can be measured using a powder resistivity measuring device (manufactured by Nittoseiko Analytech: Loresta GP-Powder Resistivity Measuring System MCP-PD-51).

[0069] The carbon purity of the raw material carbon nanotubes is represented by the content (%) of carbon atoms in the carbon nanotubes. The carbon purity is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 98% by mass or more relative to 100% by mass of the carbon nanotubes.

[0070] The amount of metal contained in the raw material carbon nanotubes is preferably 10% by mass or less, more preferably 5% by mass or less, and further preferably 2% by mass or less relative to 100% by mass of the carbon nanotubes. Examples of the metal contained in the carbon nanotubes include metals or metal oxides used as catalysts when synthesizing carbon nanotubes. Specifically, examples include metals such as cobalt, nickel, aluminum, magnesium, silicon dioxide, manganese, or molybdenum, metal oxides, or composite oxides thereof.

[0071] The raw material carbon nanotubes usually exist as secondary particles. The shape of the secondary particles may be, for example, a state in which carbon nanotubes as general primary particles are intricately entangled. It may also be an aggregate of secondary particles in which carbon nanotubes are made straight. The secondary particles of the aggregate of straight carbon nanotubes are easier to untie than the entangled carbon nanotubes. In addition, the straight carbon nanotubes have better dispersibility than the entangled carbon nanotubes, and therefore can be preferably used as carbon nanotubes.

[0072] The raw material carbon nanotubes may be surface-treated carbon nanotubes. Alternatively, the raw material carbon nanotubes may be carbon nanotube derivatives endowed with functional groups represented by carboxyl groups. Alternatively, carbon nanotubes containing organic compounds, metal atoms, or substances represented by fullerenes may be used.

[0073] The raw material carbon nanotubes may also be carbon nanotubes produced by any method. Carbon nanotubes can generally be produced by laser ablation, arc discharge, thermal chemical vapor deposition (CVD), plasma CVD and combustion, but are not limited thereto. For example, in an environment where the oxygen concentration is less than 1% by volume, at 500°C to 1000°C, a carbon source and a catalyst are contacted and reacted to produce carbon nanotubes. The carbon source may be at least one of a hydrocarbon and an alcohol.

[0074] Any previously known raw material gas can be used as the raw material gas that becomes the carbon source of the raw material carbon nanotubes. For example, as the raw material gas containing carbon, hydrocarbons represented by methane, ethylene, propane, butane and acetylene, carbon monoxide, and alcohols can be used, but they are not limited to these. In particular, from the perspective of ease of use, it is ideal to use at least one of hydrocarbons and alcohols as the raw material gas.

[0075] [Handling solvent]

[0076] As the treatment solvent for wet mixing of carbon nanotubes with an average diameter of 3nm to 30nm, a highly polar alcoholic solvent or water is preferred. By using a highly polar alcoholic solvent or water for treatment, the polarity difference with the surface of the hydrophobic carbon nanotubes becomes larger, and the carbon nanotubes condense with each other, which is advantageous in promoting bundle formation, so it is preferred.

[0077] The so-called high polarity means that the value of the Hansen solubility parameters (SP value) at 25°C is greater than 10. The Hansen solubility parameters (SP value) at 25°C can be calculated by the Hansen solubility parameter application software (Hansen Solubility Parameters in Practice (HSPiP) Version (Ver.) 5.1.05, developed by Dr. Hansen, Prof. Abbott, Dr. Yamamoto).

[0078] As the alcohol solvent with high polarity, for example, ethanol, propanol, and butanol can be cited, but it is not limited to the exemplified solvents as long as the mixing state with the carbon nanotubes is the most suitable. The SP values ​​of monovalent aliphatic alcohols are shown below. Methanol (SP value: 14.4, the same below), ethanol (13.0), 2-propanol (isopropyl alcohol, IPA) (11.5), 1-butanol (11.3), 2-butanol (10.8), 2-methyl-1-propanol (11.1), 2-methyl-2-propanol (10.6), 1-pentanol (10.7), 2-pentanol (10.5), isopentanol (10.4), tert-pentanol (10.3).

[0079] [Wet Mixing]

[0080] As the apparatus used for wet mixing, for example, there can be mentioned mixers such as dispersers, homomixers, or planetary mixers, homogenizers such as "Clearmix" manufactured by M-technique and "Filmix" manufactured by PRIMIX, paint conditioners manufactured by Red Devil, sand mills such as "Dyno-mill" manufactured by Shinmaru Enterprises, attritors, or co-ball mills, media dispersers such as "Jenius PY" manufactured by Jenius, and "SUGINO TECHNOLOGY" manufactured by Sugino Machinery. The present invention can be a wet jet mill such as "Starburst" manufactured by Nanomizer Co., Ltd., "nanomizer" manufactured by Nanomizer Co., Ltd., "clear SS-5" manufactured by M-technique Co., Ltd., or "MICROS" manufactured by Nara Machinery Co., Ltd., or other media-free dispersers, but is not limited to these.

[0081] In addition, as a wet mixing device, it is sometimes preferred to use a device that has been processed to prevent the metal from being mixed into the device. For example, in the case of using a medium-type disperser, it is preferred to use a method in which the agitator and the vessel are ceramic or resin-made dispersers; or a disperser after the surface of the metal agitator and the container is treated with tungsten carbide thermal spraying or resin coating. As a medium, it is preferred to use ceramic beads such as glass beads, zirconium oxide beads, or aluminum oxide beads. In addition, regarding the use of a roller mill, it is also preferred to use a ceramic roller. The dispersion device can use only one, or a combination of multiple devices can be used.

[0082] [Boron source]

[0083] When the carbon nanotubes are wet-mixed with the treatment solvent, a boron source may be included. It is speculated that by wet-treating in the presence of the boron source and the treatment solvent, the boron source and the carbon nanotubes are uniformly mixed, and the formation of a bundle structure in which a plurality of carbon nanotubes are connected is promoted by the calcination process. Moreover, the treated carbon nanotubes obtained in this way maintain a bundle shape even after dispersion, and a carbon nanotube dispersion showing excellent cycle characteristics can be obtained.

[0084] When a boron source is used, it is preferred to dissolve the boron source in a treatment solvent and then treat the raw carbon nanotubes. By treating in this order, the boron source and the carbon nanotubes are more uniformly mixed, and excellent cycle characteristics are exhibited.

[0085] The boron source is not particularly limited, and examples thereof include boron carbide, boron oxide, boron nitride, metal boride, boron oxyacid, borane, and boron-containing organic compounds. Specifically, boron carbide includes B4C (B 12 C3) and B 12 C2 (B6C), etc., boron oxides include BC2O, BCO2, B2O2, B2O3, B4O3, B4O5, etc., boron nitrides include BN, etc., metal borides include AlB2, CoB, FeB, MgB2, NiB, TiB2, etc., boron oxygen acids include orthoboric acid, metaboric acid, tetraboric acid, etc., boranes include monoborane, diborane, decaborane, etc., boron-containing organic compounds include borate esters such as trimethyl borate and triethyl borate, substituted boranes such as triethylborane and triphenylborane, phenylboric acid, phenylboric acid esters, etc.

[0086] From the viewpoint of forming a bundle shape, the boron source preferably has high solubility in the treatment solvent, and boric acid is more preferably used. The raw carbon nanotubes are wet treated in the presence of a treatment solvent or a treatment solvent and a boron source, and then heat treated (calcined) to obtain treated carbon nanotubes.

[0087] When a boron source is used, the mass ratio of the raw carbon nanotubes to the boron source is not particularly limited. The ratio of the boron source to 100 parts by mass of the raw carbon nanotubes is preferably 0.01 to 300 parts by mass, more preferably 0.05 to 100 parts by mass, and even more preferably 0.1 to 50 parts by mass.

[0088] When the raw materials are not uniformly dissolved or dispersed, a dispersant may be added as necessary to disperse or mix the raw materials in order to improve the wettability and dispersibility of the raw materials in the solvent.

[0089] The temperature conditions for heating the mixture of the raw carbon nanotubes and the boron source vary depending on the type or amount of the raw carbon nanotubes or the boron source, and are not particularly limited, but are preferably 1000° C. to 3000° C., more preferably 1100° C. to 2500° C., and further preferably 1200° C. to 2000° C. In addition, the heating time is not particularly limited, but is preferably 10 minutes to 72 hours, and more preferably 30 minutes to 10 hours.

[0090] In order to prevent side reactions such as oxidation of the raw materials, the atmosphere in the heat treatment step is preferably an inert gas such as nitrogen or argon, or an atmosphere under vacuum.

[0091] The heat treatment process may be performed not only in one step under a certain environment, temperature, and time, but also in multiple steps under a certain environment, temperature, and time.

[0092] <Solvent>

[0093] Next, the solvent used in the carbon nanotube dispersion of the present invention is described. The solvent is not particularly limited as long as it is a solvent capable of dispersing carbon nanotubes, and is preferably water or any one of an organic solvent, or a mixed solvent comprising two or more solvents, and further preferably water or a solvent comprising any one of a water-soluble organic solvent, or a mixed solvent comprising any two or more of a water-soluble organic solvent. In addition, when using a dispersant described later, it is preferably a solvent that can partially or completely dissolve the dispersant, and the solvent is not particularly limited, and preferably comprises water or a water-soluble organic solvent.

[0094] Examples of organic solvents include alcohols (methanol, etc.), polyols (ethylene glycol, etc.), polyol ethers (ethylene glycol monomethyl ether, etc.), amines (ethanolamine, etc.), amides (N-methyl-2-pyrrolidone (NMP), etc.), heterocyclics (γ-butyrolactone, etc.), sulfoxides (dimethyl sulfoxide, etc.), sulfones (cyclopentane, etc.), aromatics (toluene, xylene, etc.), hydrocarbons (hexane, etc.), lower ketones (acetone, etc.), esters (ethyl acetate, etc.), and the like.

[0095] As preferred water-soluble organic solvents, amides (N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP), N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N-methylcaprolactam, etc.), heterocyclics (cyclohexylpyrrolidone, 2-oxazolidinone, 1,3-dimethyl-2-imidazolidinone, γ-butyrolactone, etc.), sulfoxides (dimethyl sulfoxide, etc.), sulfones (hexamethylphosphorotriamide, cyclopentane sulfone, etc.), alcohols (methanol, ethanol, etc.), polyols (ethylene glycol, diethylene glycol, etc.), lower ketones (acetone, methyl ethyl ketone, etc.), and tetrahydrofuran, urea, acetonitrile, etc. can be used.

[0096] <Dispersant>

[0097] The carbon nanotube dispersion of the present disclosure may further contain a dispersant. The dispersant serves to release the agglomeration of the carbon nanotubes and improve the stability of the dispersion. The dispersant is not particularly limited within the range that can stabilize the dispersion of the carbon nanotubes, and for example, a surfactant or a resin-type dispersant can be used. Surfactants are mainly classified into anionic, cationic, nonionic and amphoteric. A preferred type of dispersant can be suitably used in a preferred amount according to the characteristics required for the dispersion of the carbon nanotubes.

[0098] Examples of anionic surfactants include, but are not limited to, fatty acid salts, polysulfonates, polycarboxylates, alkyl sulfate ester salts, alkyl aryl sulfonates, alkyl naphthalene sulfonates, dialkyl sulfonates, dialkyl sulfosuccinates, alkyl phosphates, polyoxyethylene alkyl ether sulfates, polyoxyethylene alkyl aryl ether sulfates, naphthalenesulfonic acid formalin condensates, polyoxyethylene alkyl phosphoric acid sulfonates, glyceryl borate fatty acid esters, and polyoxyethylene glyceryl fatty acid esters. Specifically, examples include sodium dodecylbenzenesulfonate, sodium laurate sulfate, sodium polyoxyethylene lauryl ether sulfate, polyoxyethylene nonylphenyl ether sulfate, and sodium salts of β-naphthalenesulfonic acid formalin condensates.

[0099] Examples of the cationic surfactant include alkylamine salts and quaternary ammonium salts. Specifically, examples include stearylamine acetate, trimethyl cocoyl ammonium chloride, trimethyl tallow ammonium chloride, dimethyl dioleyl ammonium chloride, methyl oleyl diethanol chloride, tetramethyl ammonium chloride, lauryl pyridinium chloride, lauryl pyridinium bromide, lauryl pyridinium disulfate, cetyl pyridinium bromide, 4-alkylthiopyridine, poly(vinylpyridine)-dodecyl bromide, and dodecylbenzyltriethylammonium chloride.

[0100] Examples of the nonionic surfactant include, but are not limited to, polyoxyethylene alkyl ethers, polyoxyalkylene derivatives, polyoxyethylene phenyl ethers, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, and alkyl allyl ethers. Specifically, polyoxyethylene lauryl ether, sorbitan fatty acid esters, and polyoxyethylene octyl phenyl ethers are included.

[0101] As an amphoteric surfactant, aminocarboxylate is mentioned, for example.

[0102] The surfactant may be used alone or in combination of two or more surfactants. For example, a combination of anionic surfactant and nonionic surfactant, or a combination of cationic surfactant and nonionic surfactant may be used. The blending amount at this time is preferably set to a blending amount that is preferred relative to each surfactant component. As a combination, a combination of anionic surfactant and nonionic surfactant is preferred. The anionic surfactant is preferably a polycarboxylate. The nonionic surfactant is preferably polyoxyethylene phenyl ether.

[0103] Examples of the resin dispersant include cellulose derivatives (cellulose acetate, cellulose acetate butyrate, cellulose butyrate, cyanoethyl cellulose, ethyl hydroxyethyl cellulose, nitrocellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, etc.), polyvinyl alcohol, polyvinyl butyral, polyvinyl pyrrolidone, polyacrylonitrile polymers, polyacrylic acid, and various rubbers.

[0104] Particularly preferred are methyl cellulose, ethyl cellulose, carboxymethyl cellulose, polyvinyl alcohol, polyvinyl butyral, polyvinyl pyrrolidone, polyacrylonitrile polymers, polyacrylic acid, and various rubbers (eg, partially hydrogenated nitrile rubber).

[0105] Regarding the resin-type dispersant, it is particularly preferred to use a polymer containing one or more selected from the group of a nitrile-containing structural unit, a carboxyl-containing structural unit, a hydroxyl-containing structural unit, and a heterocyclic-containing structural unit as a structural unit to improve the adsorption of boron-containing carbon nanotubes and the affinity for the medium. The polymer preferably contains an alkylene structure in the main chain. By having any one of the nitrile group, carboxyl group, hydroxyl group, and heterocyclic structure with strong polarization, the adsorption of carbon nanotubes and the affinity for the medium can be improved, so that the carbon nanotubes are stably present in the medium. In addition, if the polymer contains two or more selected from the group of a nitrile-containing structural unit, a carboxyl-containing structural unit, a hydroxyl-containing structural unit, and a heterocyclic-containing structural unit, the adsorption of carbon nanotubes and the affinity for the medium are further improved, which is more preferred.

[0106] The structural unit containing nitrile groups is a structural unit containing nitrile groups, preferably a structural unit containing an alkylene structure substituted with a substituent containing nitrile groups. The alkylene structure is preferably a linear or branched alkylene structure. The number of nitrile groups contained in the structural unit containing nitrile groups is preferably one or two, more preferably one. The method for introducing the structural unit containing nitrile groups into the polymer is not particularly limited, for example, a method for preparing a polymer by a polymerization reaction of a monomer containing nitrile groups can be preferably used.

[0107] As monomers containing nitrile groups, for example, acrylonitrile, methacrylonitrile, fumaronitrile, etc. can be cited, and one can be used alone, or two or more can be used in combination. In particular, from the perspective of improving the intermolecular force between polymers and / or between polymers and dispersed substances (adsorbed substances), the ease of obtaining raw materials, and reactivity, the monomer containing nitrile groups is preferably acrylonitrile. The content of the structural unit containing nitrile groups is based on the mass of the polymer (that is, when the mass of the polymer is set to 100% by mass), preferably 15% by mass or more, more preferably 20% by mass or more, and further preferably 30% by mass or more. In addition, it is preferably 100% by mass or less, more preferably 90% by mass or less, and further preferably 85% by mass or less. It is believed that by setting the content of the structural unit containing nitrile groups to the range, the adsorption of the dispersed substance and the affinity for the dispersion medium can be controlled, and the dispersed substance can be stably present in the dispersion medium. In addition, it is believed that the affinity of the polymer for the electrolyte can also be controlled, which can prevent the polymer from dissolving in the electrolyte in the battery and increasing the resistance of the electrolyte.

[0108] The carboxyl-containing structural unit is a structural unit containing a carboxyl group, preferably a structural unit containing an alkylene structure substituted with a substituent containing a carboxyl group. The alkylene structure is preferably a linear or branched alkylene structure. The number of carboxyl groups contained in the carboxyl-containing structural unit is preferably one or two, more preferably one. The method for introducing the carboxyl-containing structural unit into the polymer is not particularly limited, for example, a method for preparing a polymer by a polymerization reaction of a monomer containing a carboxyl group, or a method for preparing a polymer by a polymerization reaction of a monomer containing a functional group other than a carboxyl group and modifying it to a carboxyl group.

[0109] Examples of carboxyl-containing monomers include unsaturated fatty acids such as (meth)acrylic acid, crotonic acid, itaconic acid, maleic acid, fumaric acid, and citraconic acid, 2-(meth)acryloyloxyethyl phthalate, and 2-(meth)acryloyloxypropyl phthalate. In addition, carboxyl-containing monomers may be obtained by hydrolyzing the carboxyl group of a polymer obtained by polymerization of carboxyl-containing monomers such as (meth)acrylamide. The carboxyl-containing monomer is preferably an unsaturated fatty acid, more preferably (meth)acrylic acid, and further preferably acrylic acid.

[0110] From the viewpoint of having moderate affinity with the solvent, the content of the structural unit containing a carboxyl group is based on the mass of the polymer (that is, when the mass of the polymer is set to 100 mass%), preferably 60 mass% or more, more preferably 80 mass% or more, and preferably 98 mass% or less, and can also be 100 mass%. In addition, if it also contains one or more of the group of structural units selected from nitrile-containing units, hydroxyl-containing structural units, and heterocyclic structural units, the affinity of the carbon nanotubes to the medium becomes higher, which is more preferred. In the case of also containing one or more of the group of structural units selected from nitrile-containing units, hydroxyl-containing structural units, and heterocyclic structural units, the content of the structural unit containing a carboxyl group is based on the mass of the polymer (that is, when the mass of the polymer is set to 100 mass%), preferably 3 mass% or more, more preferably 10 mass% or more, and further preferably 15 mass% or more. In addition, from the viewpoint of electrolyte resistance, it is preferably 50 mass% or less, more preferably 35 mass% or less, and further preferably 30 mass% or less.

[0111] The hydroxyl-containing structural unit is a structural unit containing a hydroxyl group, preferably a structural unit containing an alkylene structure substituted with a substituent containing a hydroxyl group. The alkylene structure is preferably a linear or branched alkylene structure. The number of hydroxyl groups contained in the hydroxyl-containing structural unit is preferably one or two, more preferably one. The method for introducing a hydroxyl-containing structural unit into a polymer is not particularly limited, and examples thereof include: a method for preparing a polymer by a polymerization reaction of a monomer containing a hydroxyl group, or a method for preparing a polymer by a polymerization reaction of a monomer containing a functional group other than a hydroxyl group and modifying it to a hydroxyl group.

[0112] Examples of the monomer containing a hydroxyl group include 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, glycerol mono(meth)acrylate, 4-hydroxyvinylbenzene, 2-hydroxy-3-phenoxypropyl acrylate, or caprolactone adducts of these monomers (addition mole number is 1 to 5). The monomer containing a hydroxyl group is preferably a hydroxyalkyl (meth)acrylate, more preferably 2-hydroxyethyl (meth)acrylate, and still more preferably 2-hydroxyethyl acrylate.

[0113] As a method for preparing a polymer by polymerization reaction of a monomer containing a functional group other than a hydroxyl group and modifying it to a hydroxyl group, for example, there can be mentioned a method (saponification reaction) in which vinyl acetate is polymerized and the acetyl group of the obtained polyvinyl acetate is saponified with a base such as sodium hydroxide to convert it into a hydroxyl group. The saponification reaction rate (saponification degree) can be arbitrarily controlled by changing the concentration of sodium hydroxide and the treatment time.

[0114] In addition, for the purpose of improving the affinity between carbon nanotubes and the medium, the hydroxyl group in the polymer can be reacted with an aldehyde compound to modify it into an acetal group for use (acetalization). The aldehyde compound used in the acetalization reaction can be, for example, a linear, branched, cyclic saturated, unsaturated, or aromatic aldehyde compound with a carbon number of 1 to 15, but is not limited to these. Specifically, formaldehyde, acetaldehyde, propionyl aldehyde, n-butyraldehyde, isobutyraldehyde, tert-butyraldehyde, benzaldehyde, etc. can be listed. These aldehyde compounds can be used alone or in combination of two or more. From the perspective of versatility, linear, branched, cyclic saturated, unsaturated, or aromatic aldehyde compounds with a carbon number of 1 to 10 are preferred, and linear aldehyde compounds with a carbon number of 1 to 4 are more preferred. By changing the aldehyde compound and the treatment time, the reaction rate of acetalization (acetalization degree) can be arbitrarily controlled.

[0115] The content of the hydroxyl-containing structural unit is based on the mass of the polymer (i.e., when the mass of the polymer is set to 100 mass%), preferably 80 mass% or more, more preferably 85 mass% or more, and preferably 99.8 mass% or less. Among them, in the case of also containing one or more of the group of nitrile-containing structural units, hydroxyl-containing structural units, and heterocyclic structural units, it is preferably 5 mass% or more, and preferably 95 mass% or less, and more preferably 85 mass% or less. By setting it to the range, polarization can be enhanced and the affinity for carbon nanotubes and media can be improved. In addition, it is also preferred from the perspective of electrolyte resistance. For the same reason as the content of the hydroxyl-containing structural unit, the content of the acetal group is preferably set within the preferred range of the content of the hydroxyl-containing structural unit.

[0116] The heterocyclic structural unit is a structural unit containing a heterocyclic structure, and more preferably a structural unit containing an alkylene structure substituted by a substituent containing a heterocyclic structure. The alkylene structure is preferably a linear or branched alkylene structure. The heterocyclic ring contained in the heterocyclic structural unit may be a monocyclic structure or a condensed ring structure, preferably a monocyclic structure. In addition, the number of heterocyclic rings contained in the heterocyclic structural unit is preferably one or two, and more preferably one. The heterocyclic ring contains atoms other than carbon in the atoms constituting the ring, for example, one or more nitrogen atoms, oxygen atoms, sulfur atoms, etc. As atoms other than carbon constituting the ring, nitrogen or oxygen is preferably used, and nitrogen is more preferably used. If atoms other than carbon are contained in the atoms constituting the ring, polarization is generated in the heterocyclic ring, which can strongly act on the carbon nanotubes. In addition, the method for introducing heterocyclic rings into polymers is not particularly limited, and for example, a method for preparing polymers by polymerization reaction of monomers containing heterocyclic rings can be used.

[0117] As a monomer containing a heterocycle, an N-vinyl cyclic amide structural unit is preferred, for example, N-vinyl-2-pyrrolidone, N-vinyl-ε-caprolactam, N-vinyl-2-piperidone, N-vinyl-3-morpholinone, N-vinyl-1,3-oxazine-2-one, N-vinyl-3,5-morpholinedione, etc. In particular, from the perspective of improving battery characteristics, N-vinyl-2-pyrrolidone is preferred. In addition, these can be used alone or in combination of two or more.

[0118] From the viewpoint of enhancing the effect on the carbon nanotubes, the content of the heterocyclic ring-containing structural unit is preferably 70% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, particularly preferably 95% by mass or more, and may also be 100% by mass, based on the mass of the polymer (i.e., when the mass of the polymer is set to 100% by mass).

[0119] The polymer may further include one or more structural units selected from the group consisting of structural units containing active hydrogen groups (excluding carboxyl groups and hydroxyl groups), structural units containing basic groups, and structural units containing ester groups as other structural units. By selecting and including the structural units in combination with the hydrophilicity, hydrophobicity, acidity, alkalinity, etc. of the base material or the material to be mixed with the conductive material dispersion of the present disclosure, the conductive material dispersion can be applied in various applications.

[0120] The structural unit containing an active hydrogen group is a structural unit having, for example, a primary amino group, a secondary amino group, a thiol group, etc. as an active hydrogen group. Here, the so-called "primary amino group" refers to -NH2 (amino group), and the so-called "secondary amino group" refers to a group formed by replacing a hydrogen atom on a primary amino group with an organic residue such as an alkyl group. However, in this specification, the primary amino group and the secondary amino group in the acid amide are not included in the active hydrogen group.

[0121] The basic group-containing structural unit is a structural unit having a basic group. Examples of the basic group include a tertiary amino group, an amide group, and the like. In addition, a structural unit having a primary amino group and a structural unit having a secondary amino group may also be included in the basic group-containing structural unit, but in the present disclosure, they are treated as the active hydrogen group-containing structural unit and are not included in the basic group-containing structural unit.

[0122] The ester group-containing structural unit is a structural unit having a structure represented by (R1)2C=CH-CO-O-R2 (wherein R1 is a hydrogen atom or a methyl group and at least one of them is a hydrogen atom, and R2 is an alkyl group which may have a substituent).

[0123] Furthermore, the structural unit including the active hydrogen group or the basic group as a substituent of the alkyl group is treated as the active hydrogen group-containing structural unit or the basic group-containing structural unit, and is not included in the ester group-containing structural unit.

[0124] When a polymer is used as a dispersant in a carbon nanotube dispersion, the polymer content is preferably determined based on the specific surface area and wettability of the carbon nanotubes, and is preferably 2% by mass or more, more preferably 20% by mass or more, and further preferably 30% by mass or more, when the mass of the treated carbon nanotubes is set to 100% by mass. In addition, it is preferably 250% by mass or less, more preferably 150% by mass or less, and further preferably 100% by mass or less.

[0125] The dispersant preferably contains at least a polymer. The dispersant may further contain any polymer, any copolymer, etc. The content of the polymer in the dispersant is preferably 50% by mass or more, more preferably 80% by mass or more, more preferably 90% by mass or more. The content of the polymer in the dispersant may be 100% by mass, in which case the dispersant consists only of the polymer.

[0126] The pH value of the carbon nanotube dispersion disclosed in the present invention can generally be used in the range of 4 to 12. Preferably, it is in the range of 4 to 6. It is believed that by adjusting the pH value to within the range, the wettability of the carbon nanotubes can be improved, and the role of the polymer as a dispersant can be improved. If the pH value is outside the range, the dispersibility of the carbon nanotubes may be reduced or the binder may be gelled. In addition, when used for battery applications, it may be easy to cause problems such as corrosion of various raw materials and outer packaging materials in the battery.

[0127] When water is included as a solvent, the pH of the carbon nanotube dispersion can be measured using a general pH meter. On the other hand, when water is not substantially contained as a solvent, for example, when only NMP is selected as a solvent, it refers to a value obtained by adding water to the carbon nanotube dispersion and adjusting the solid content concentration after adding water to 50% when the solid content concentration before adding water is set to 100%, and measuring using a general pH meter, and can be measured, for example, by the following method.

[0128] While stirring the carbon nanotube dispersion having a solid content concentration of 5% by using a disperser, water is added to adjust the solid content concentration of the carbon nanotube dispersion to 2.5%. After stirring evenly, the pH of the carbon nanotube dispersion can be measured at 25°C using a tabletop pH meter (Seven Compact S220 Expert Pro, manufactured by Mettler-Toledo).

[0129] In addition, in the present disclosure, substantially no water is contained, which means that water is not intentionally added. The water content is preferably 5% by mass or less, more preferably 1% by mass or less, and further preferably 0.5% by mass or less, based on the mass of the solvent.

[0130] The pH value of the carbon nanotube dispersion is not particularly limited and can be adjusted by (1) the amount of metal hydroxide contained in the carbon nanotubes, (2) the type or amount of functional groups on the surface of the carbon nanotubes, and (3) the type or amount of the added alkali. By adjusting the pH value by combining the above factors (1) to (3), not only the wettability of the carbon nanotubes can be improved, but also a carbon nanotube dispersion having excellent dispersibility and stability can be obtained.

[0131] As described above, in the production process of carbon nanotubes, metals, metal oxides, and metal hydroxides used as catalysts remain in the system. The pH value can be adjusted by appropriately adjusting the amount of metals remaining in the carbon nanotubes, especially the content of the metal hydroxide described in (1). The amount of residual metals, carbon purity, and pH value of the carbon nanotube dispersion containing the carbon nanotubes can be adjusted by a conventionally known purification treatment method.

[0132] The functional groups on the surface of the carbon nanotubes in (2) are not particularly limited, and examples thereof include carboxyl groups, sulfonic groups, and hydroxyl groups. The method for introducing functional groups into carbon nanotubes is not particularly limited. For example, in order to introduce carboxyl groups into carbon nanotubes, it is sufficient to heat them together with an acid having an oxidizing effect. The above operation is relatively easy, and a reactive carboxyl group can be added, so it is preferred. As an acid having an oxidizing effect, concentrated nitric acid, hydrogen peroxide water, a mixed solution of sulfuric acid and nitric acid, aqua regia, etc. can be mentioned. In particular, when concentrated nitric acid is used, its concentration is preferably 5% by mass or more, and more preferably 60% by mass or more. Heating can be carried out by conventional methods, and its temperature is preferably below the boiling point of the acid used. For example, if it is concentrated nitric acid, it is preferably in the range of 50°C to 130°C. In addition, as the heating time, it is preferably in the range of 30 minutes to 20 hours, and more preferably in the range of 1 hour to 8 hours. The carbon nanotubes preferably do not have acidic functional groups such as carboxyl groups or sulfonic groups. If a large amount of acidic functional groups are contained, the carbon nanotube dispersion may gel during storage.

[0133] The base added for adjusting the pH in (3) is not particularly limited, and specifically, at least one base selected from the group consisting of inorganic bases, inorganic metal salts, organic hydroxides, and other organic bases can be used.

[0134] As inorganic bases and inorganic metal salts, for example, chlorides, hydroxides, carbonates, nitrates, sulfates, phosphates, tungstates, vanadates, molybdates, niobates, or borates of alkali metals or alkaline earth metals; and ammonium hydroxide, etc. Among these, chlorides, hydroxides, carbonates, and alkoxides of alkali metals and alkaline earth metals are preferred from the viewpoint of being able to easily supply cations. As hydroxides of alkali metals, for example, lithium hydroxide, sodium hydroxide, potassium hydroxide, etc. can be listed. As hydroxides of alkaline earth metals, for example, calcium hydroxide, magnesium hydroxide, etc. can be listed. Alkali metal carbonates can be listed, for example, lithium carbonate, lithium bicarbonate, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, etc. Alkali metal alkoxides can be listed, for example, lithium methoxide, lithium ethoxide, lithium n-butoxide, lithium tert-butoxide, potassium methoxide, potassium ethoxide, potassium n-butoxide, potassium tert-butoxide, sodium methoxide, sodium ethoxide, sodium n-butoxide, sodium tert-butoxide, etc. The carbon number of the alkoxide can be 5 or more. Examples of the alkoxide of an alkaline earth metal include magnesium methoxide, magnesium ethoxide, magnesium n-butoxide, magnesium tert-butoxide, etc. The alkoxide may have 5 or more carbon atoms.

[0135] Among these, lithium hydroxide, sodium hydroxide, potassium hydroxide, lithium carbonate, sodium carbonate, lithium tert-butoxide, potassium tert-butoxide, and sodium tert-butoxide are more preferable. In addition, the inorganic base of the present disclosure and the metal contained therein may be a transition metal.

[0136] Organic hydroxides are salts containing organic cations and hydroxide ions. Examples of organic hydroxides include trimethyl-2-hydroxyethylammonium hydroxide, tetramethylammonium hydroxide, cetyltrimethylammonium hydroxide, hexadecyltrimethylammonium hydroxide, trimethylphenylammonium hydroxide, 3-trifluoromethyl-phenyltrimethylammonium hydroxide, and benzyltrimethylammonium hydroxide. Among these, trimethyl-2-hydroxyethylammonium hydroxide and tetramethylammonium hydroxide are particularly preferred.

[0137] As other organic bases, methylamine, ethylamine, propylamine, butylamine, hexylamine, octylamine, dioctylamine, trioctylamine, aminoethanol, aminopropanol, aminobutanol, 2-methoxyethylamine, etc. can be listed. These organic bases have high solubility in the electrolyte, so if the amount used is too much, it is possible to reduce the battery performance. In addition, these compounds are easily decomposed, so the decomposed products are likely to remain in the coating film, and if they are present in the battery, the initial capacity is likely to be reduced.

[0138] The amount of the alkali used is based on the mass of the polymer, preferably 1% by mass or more, more preferably 2% by mass or more, and further preferably 3% by mass or more. The amount of the alkali used is based on the mass of the polymer, preferably 20% by mass or less, more preferably 15% by mass or less, and further preferably 10% by mass or less. If the amount used is too much, the stability of the obtained carbon nanotube dispersion may become poor. Furthermore, it may become a cause of corrosion in the dispersion device and / or the battery.

[0139] The reason why dispersibility is improved by adjusting the pH to a predetermined value is not clear, but the following main factors are considered. The reason why dispersibility is improved is not limited to the main factors listed in the following (1) to (3).

[0140] (1) Improve the dispersibility of polymers.

[0141] By adjusting the pH value to a predetermined value, the adsorption of the polymer containing one or more selected from the group consisting of a nitrile group-containing structural unit, a carboxyl group-containing structural unit, a hydroxyl group-containing structural unit, and a heterocyclic ring-containing structural unit to the dispersed matter can be improved. In addition, since the functional group possessed by the structural unit can form a hydrogen bond, it is considered that a cross-linked structure based on hydrogen bonds can be introduced into the molecules of the polymer and the polymer can be three-dimensionally adsorbed to the dispersed matter, and a dispersion having not only excellent dispersibility but also excellent stability can be obtained.

[0142] (2) Reduce the solution viscosity of the polymer.

[0143] When a polymer is dissolved in a solvent and used, if the viscosity of the polymer solution is low, it is thought that the dispersant can easily enter the interior of the carbon nanotubes having a strong cohesive force, thereby obtaining a uniform dispersion.

[0144] (3) Improve the wettability of carbon nanotubes.

[0145] When carbon nanotubes are dispersed, the carbon nanotubes are wetted with a solvent to reduce the cohesive force between the carbon nanotubes, and then crushed to stabilize them, so that they can exist in the form of a dispersion. Carbon nanotubes have significantly lower wettability than other conductive materials, so it is necessary to improve the wettability by pre-treatment such as chemical treatment or mechanical crushing of the carbon nanotubes, but these treatments may lead to reduced conductivity. It is believed that by adjusting the pH value to a specified value, wettability can be dramatically improved without damaging the conductivity of the carbon nanotubes.

[0146] In addition, the carbon nanotube dispersion of the present disclosure may contain a defoaming agent in addition to the dispersant. Any defoaming agent, such as a commercially available defoaming agent, a wetting agent, a hydrophilic organic solvent, a water-soluble organic solvent, etc., having a defoaming effect may be used, and one or more types may be used in combination.

[0147] For example, alcohols include ethanol, propanol, isopropanol, butanol, octyl alcohol, hexadecyl alcohol, acetylene alcohol, ethylene glycol monobutyl ether, methyl cellosolve, butyl cellosolve, propylene glycol monomethyl ether, acetylene glycol, polyoxyalkylene glycol, propylene glycol, and other glycols; fatty acid esters include diethylene glycol laurate, glyceryl monoricinoleate, alkenyl succinic acid derivatives, sorbitan monolaurate, sorbitan trioleate, polyoxyethylene monolaurate, sorbitan trioleate ... Lauric acid ester, polyoxyethylene sorbitan monolaurate, natural wax, etc., amide series: polyoxyalkylene amide, acrylate polyamine, etc., phosphate ester series: tributyl phosphate, sodium octyl phosphate, etc., metal soap series: aluminum stearate, calcium oleate, etc., oil series: animal and vegetable oils, sesame oil, castor oil, etc., mineral oil series: kerosene, paraffin, etc., silicone series: dimethyl silicone oil, silicone cream, silicone emulsion, organic modified polysiloxane, fluorosilicone oil, etc.

[0148] <Other conductive materials>

[0149] In the carbon nanotube dispersion of the present disclosure, in addition to carbon nanotubes, other conductive materials may be arbitrarily included. As other conductive materials, for example, metal powders such as gold, silver, copper, silver-plated copper powder, silver-copper composite powder, silver-copper alloy, amorphous copper, nickel, chromium, palladium, rhodium, ruthenium, indium, silicon, aluminum, tungsten, molybdenum, platinum, etc., inorganic powders coated with these metals, powders of metal oxides such as silver oxide, indium oxide, tin oxide, zinc oxide, ruthenium oxide, inorganic powders coated with these metal oxides, and carbon materials such as carbon black and graphite. Other conductive materials may be used alone or in combination of two or more. When other conductive materials are used, carbon black is preferably used from the viewpoint of the adsorption performance of the dispersant. Other conductive materials are substances (materials) different from the electrode active material described later.

[0150] Examples of carbon black include acetylene black, furnace black, hollow carbon black, channel black, thermal black, Ketjen black, etc. Carbon black may be neutral, acidic, or basic, and oxidized carbon black or graphitized carbon black may also be used.

[0151] <Manufacturing of Carbon Nanotube Dispersion Liquid>

[0152] The carbon nanotube dispersion disclosed herein comprises bundled carbon nanotubes and a solvent, and preferably further comprises a dispersant. In order to obtain the carbon nanotube dispersion disclosed herein, it is preferred to perform a process in which the treated carbon nanotubes described above are dispersed in a solvent. The dispersing device used for the process is not particularly limited.

[0153] As the dispersing device, a dispersing machine commonly used in pigment dispersion, etc. can be used. For example, mixers such as dispersers, homomixers, and planetary mixers, homogenizers (Advanced Digital Sonifer (registered trademark), model (MODEL) 450DA manufactured by BRANSON, "clearmix" manufactured by M-technique, "filmix" manufactured by PRIMIX, "abramix" manufactured by Silverson, etc.), paint conditioners (manufactured by Red Devil), colloid mills ("PUC colloid mill" manufactured by PUC, "colloid mill MK" manufactured by IKA), cone mills ("cone mill MKO" manufactured by IKA, etc.), ball mills, sand mills (SHINMARU The present invention also includes media dispersers such as "Dyno-mill" manufactured by Einstein EntERPRISES, etc.), attritor, pearl mill ("DCP mill" manufactured by Eirich, etc.), co-ball mill, wet jet mill ("Jenius PY" manufactured by Jenius, "Starburst" manufactured by Suginosuke Machine, "nanomizer" manufactured by Nanomizer, etc.), media-free dispersers such as "Clear SS-5" manufactured by M-technique, "MICROS" manufactured by Nara Machinery Co., Ltd., and other roller mills, but the present invention is not limited to these.

[0154] The amount of carbon nanotubes in the carbon nanotube dispersion of the present disclosure is preferably 0.2 to 20 parts by mass, more preferably 0.5 to 10 parts by mass, and even more preferably 0.5 to 3.0 parts by mass, relative to 100 parts by mass of the carbon nanotube dispersion.

[0155] The viscosity of the carbon nanotube dispersion of the present embodiment is preferably 10 mPa·s to 10000 mPa·s, more preferably 10 mPa·s to 5000 mPa·s, and even more preferably 10 mPa·s to 2000 mPa·s, as measured using a Brookfield viscometer at 60 rpm.

[0156] The carbon nanotube dispersion disclosed in the present invention not only has excellent dispersibility and conductivity, but also has improved durability against external forces such as impact or coating strength. Therefore, it can be preferably used in dispersions for forming conductive wiring or transparent conductive films, dispersions for forming electrochemical devices such as secondary batteries, capacitors or sensors, etc.

[0157] <Carbon nanotube resin composition>

[0158] The carbon nanotube resin composition disclosed herein comprises a carbon nanotube dispersion and a binder, and can be obtained by mixing the carbon nanotube dispersion and the binder and homogenizing them. As a mixing method, a conventionally known method can be used, and the dispersing device described in the carbon nanotube dispersion can be used.

[0159] <Adhesive>

[0160] The binder in the present disclosure is a resin for bonding substances such as carbon nanotubes.

[0161] The binder resin can be appropriately selected in combination with the target physical properties, for example, polymers or copolymers containing ethylene, propylene, vinyl chloride, vinyl acetate, vinyl alcohol, maleic acid, acrylic acid, acrylic acid ester, methacrylic acid, methacrylate, acrylonitrile, styrene, vinyl butyral, vinyl acetal, vinyl pyrrolidone, etc. as structural units; polyurethane resin, polyester resin, phenol resin, epoxy resin, phenoxy resin, urea resin, melamine resin, alkyd resin, acrylic resin, formaldehyde resin, silicone resin, fluororesin; cellulose resin such as carboxymethyl cellulose; rubbers such as styrene butadiene rubber and fluororubber; conductive resins such as polyaniline and polyacetylene. In addition, modified products or mixtures of these resins, and copolymers may also be used.

[0162] Among these, when used as a binder resin for the positive electrode film, in terms of tolerance, preferably a polymer or copolymer having a fluorine atom in the molecule such as polyvinylidene fluoride, polyvinyl fluoride, tetrafluoroethylene, etc. In addition, when used as a binder resin for the negative electrode film, preferably carboxymethyl cellulose, styrene butadiene rubber, polyacrylic acid, etc. having good adhesion.

[0163] Carboxymethyl cellulose preferably has a high viscosity, for example, the viscosity of a 1 mass % aqueous solution is preferably 500 to 6000 mPa·s, more preferably 1000 to 3000 mPa·s. The viscosity can be measured using a B-type viscometer at 25° C. and a rotor rotation speed of 60 rpm.

[0164] The carboxymethyl cellulose preferably has a high degree of etherification. For example, the degree of etherification is preferably 0.6 to 1.5, and more preferably 0.8 to 1.2.

[0165] The type or amount ratio of the binder can be appropriately selected in combination with the properties of coexisting substances such as carbon nanotubes and active materials. For example, when carboxymethyl cellulose is used, when the mass of the active material is set to 100 mass%, the proportion of carboxymethyl cellulose is preferably 0.5 mass% to 3.0 mass%, and more preferably 1.0 mass% to 2.0 mass%.

[0166] As long as the styrene butadiene rubber is an oil-in-water emulsion, any material generally used as a binder for an electrode can be used. When the styrene butadiene rubber is used, the proportion of the styrene butadiene rubber is preferably 0.5% to 3.0% by mass, more preferably 1.0% to 2.0% by mass, when the mass of the active material is 100% by mass.

[0167] When polyacrylic acid is used, the ratio of polyacrylic acid is preferably 1% by mass to 25% by mass, and more preferably 5% by mass to 20% by mass, based on 100% by mass of the active material.

[0168] The weight average molecular weight of these binder resins is preferably 10,000 to 2,000,000, more preferably 100,000 to 1,000,000, and still more preferably 200,000 to 1,000,000.

[0169] <Composite material slurry>

[0170] The composite material slurry disclosed in the present invention comprises the carbon nanotube resin composition and an active substance.

[0171] [Active substances]

[0172] The active material in the present disclosure is a material that serves as a basis for a battery reaction. In terms of electromotive force, active materials are divided into positive electrode active materials and negative electrode active materials.

[0173] There are no particular limitations on the positive electrode active material, and metal compounds such as metal oxides and metal sulfides that can be doped or embedded with lithium ions, and conductive polymers can be used. Examples include oxides of transition metals such as Fe, Co, Ni, and Mn, composite oxides with lithium, inorganic compounds such as transition metal sulfides, and the like. Specifically, MnO, V2O5, V6O 13, transition metal oxide powders such as TiO2, composite oxide powders of lithium and transition metals such as lithium nickelate, lithium cobaltate, lithium manganate, lithium manganate with a spinel structure, lithium iron phosphate-based materials as phosphate compounds with an olivine structure, transition metal sulfide powders such as TiS2 and FeS, etc. In addition, conductive polymers such as polyaniline, polyacetylene, polypyrrole, and polythiophene can also be used. In addition, the inorganic compounds or organic compounds can also be mixed and used.

[0174] The negative electrode active material is not particularly limited as long as it can be doped or embedded with lithium ions. For example, metal Li, alloys thereof such as tin alloys, silicon alloys, and lead alloys, Li x Fe2O3、Li x Fe3O4、Li x WO2 (x is a number where 0<x<1), metal oxides such as lithium titanate, lithium vanadate, lithium silicate, conductive polymers such as polyacetylene, polyparaphenylene, amorphous carbonaceous materials such as soft carbon or hard carbon, artificial graphite such as highly graphitized carbon materials, or carbonaceous powders such as natural graphite, carbon black, mesophase carbon black, resin calcined carbon materials, gas-grown carbon fibers, carbon fibers, etc. These negative electrode active materials can also be used alone or in combination.

[0175] As the negative electrode active material of the present disclosure, a negative electrode active material containing silicon, such as a silicon alloy or lithium silicate, that is, a silicon-based negative electrode active material is preferable.

[0176] As silicon-based negative electrode active materials, for example, there can be listed: so-called metallurgical grade silicon produced by reducing silicon dioxide with carbon; or industrial grade silicon in which impurities are reduced by acid treatment or unidirectional solidification of metallurgical grade silicon; and high-purity silicon in different crystalline states such as single crystal, polycrystalline, and amorphous, produced by reacting silicon with silane; or silicon in which the crystalline state or precipitation state is adjusted while industrial grade silicon is made high-purity by sputtering or electron beam evaporation (EB (electron beam) evaporation) method.

[0177] In addition, silicon oxide, which is a compound of silicon and oxygen, or silicon and various alloys, and silicon compounds whose crystal states are adjusted by a quenching method, etc., can also be cited. Among them, a silicon-based negative electrode active material having a structure in which silicon nanoparticles are dispersed in silicon oxide and the outside is coated with a carbon film is preferred.

[0178] In addition to using silicon-based negative electrode active materials, the negative electrode active material disclosed herein preferably uses amorphous carbonaceous materials such as soft carbon or hard carbon, artificial graphite such as highly graphitized carbon materials, or carbonaceous powders such as natural graphite. Among them, it is preferred to use carbonaceous powders such as artificial graphite or natural graphite.

[0179] When the carbonaceous powder such as artificial graphite or natural graphite is taken as 100 mass %, the amount of the silicon-based negative electrode active material is preferably 3 mass % to 50 mass %, and more preferably 5 mass % to 25 mass %.

[0180] The BET specific surface area of ​​the active material disclosed herein is preferably 0.1 m 2 / g~10m 2 / g, more preferably 0.2m 2 / g~5m 2 / g, and more preferably 0.3m 2 / g~3m 2 / g.

[0181] The average particle size of the active material disclosed herein is preferably in the range of 0.5 μm to 50 μm, more preferably 2 μm to 20 μm. The average particle size of the active material referred to in this specification is the average value of the particle size measured using an electron microscope.

[0182] [Method for producing composite material slurry]

[0183] The composite material slurry disclosed in the present invention can be prepared by various conventionally known methods, such as a method of adding an active material to a carbon nanotube resin composition, or a method of adding an active material to a carbon nanotube dispersion and then adding a binder.

[0184] In order to obtain the composite material slurry disclosed in the present invention, it is preferred to perform a process of adding an active substance to the carbon nanotube resin composition and dispersing it. The dispersing device used for the above process is not particularly limited. Regarding the composite material slurry, the composite material slurry can be obtained using the dispersing device described in the carbon nanotube dispersion.

[0185] The amount of the active material in the composite material slurry of the present disclosure is preferably 20 to 85 parts by mass, more preferably 30 to 75 parts by mass, and even more preferably 40 to 70 parts by mass, relative to 100 parts by mass of the composite material slurry.

[0186] The amount of carbon nanotubes in the composite material slurry of the present disclosure is preferably 0.01 to 10 parts by mass, preferably 0.02 to 5 parts by mass, and preferably 0.03 to 1 part by mass, relative to 100 parts by mass of the active material.

[0187] The amount of the binder in the composite material slurry of the present disclosure is preferably 0.5 to 30% by mass, more preferably 1 to 25% by mass, and particularly preferably 2 to 20% by mass, relative to 100% by mass of the active material.

[0188] The amount of solid content of the composite material slurry of the present disclosure is preferably 30 to 90% by mass, more preferably 30 to 80% by mass, and preferably 40 to 75% by mass, relative to 100% by mass of the composite material slurry.

[0189] <Conductive film and electrode film>

[0190] The conductive film disclosed herein is formed by forming a carbon nanotube dispersion into a film. For example, it is a coating film formed by coating a carbon nanotube dispersion on a sheet-like substrate and drying it. The sheet-like substrate is not particularly limited, and a conductive or non-conductive substrate can be used. As the conductive substrate, the following collector can be used.

[0191] The electrode film of the present disclosure is formed by forming the composite material slurry into a film shape, for example, a coating film in which the composite material slurry is applied on a current collector and dried to form an electrode composite material layer.

[0192] The material or shape of the current collector used in the electrode film is not particularly limited, and the material and shape suitable for various secondary batteries can be appropriately selected. For example, as the material of the current collector, metals such as aluminum, copper, nickel, titanium, or stainless steel, or alloys can be listed. In addition, as the shape, a flat foil can generally be used, but a current collector with a roughened surface, a perforated foil-shaped current collector, and a mesh-shaped current collector can also be used.

[0193] As the method for applying the composite material slurry on the collector, there is no particular restriction, and known methods can be used. Specifically, die coating, dip coating, roll coating, blade coating, spray coating, gravure coating, screen printing or electrostatic coating can be listed, and as a drying method, placement drying, air supply drying machine, warm air drying machine, infrared heating machine, far infrared heating machine, etc. can be used, but it is not particularly limited to these.

[0194] In addition, after coating, a rolling treatment using a plate pressing machine or a calender roll may be performed. The thickness of the electrode composite material layer is generally 1 μm or more and 500 μm or less, and preferably 10 μm or more and 300 μm or less.

[0195] <Non-aqueous electrolyte secondary battery>

[0196] The nonaqueous electrolyte secondary battery of the present disclosure comprises a positive electrode, a negative electrode and an electrolyte, and at least one of the positive electrode or the negative electrode comprises the electrode film. In the case where the positive electrode comprises the electrode film of the present disclosure, a composite material slurry comprising a positive electrode active material can be applied to the collector and dried to make the electrode film. In the case where the negative electrode comprises the electrode film of the present disclosure, a composite material slurry comprising a negative electrode active material can be applied to the collector and dried to make the electrode film.

[0197] As an electrolyte, various previously known electrolytes in which ions can move can be used. For example, LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, Li(CF3SO2)3C, LiI, LiBr, LiCl, LiAlCl, LiHF2, LiSCN, or LiBPh4 (wherein Ph is phenyl) etc. include electrolytes containing lithium salts, but are not limited to these, and electrolytes containing sodium salts or calcium salts can also be used. The electrolyte is preferably used as an electrolyte after being dissolved in a non-aqueous solvent.

[0198] The non-aqueous solvent is not particularly limited, and examples thereof include carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate; lactones such as γ-butyrolactone, γ-valerolactone, and γ-octalactone; glyme such as tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-methoxyethane, 1,2-ethoxyethane, and 1,2-dibutoxyethane; esters such as methyl formate, methyl acetate, and methyl propionate; sulfoxides such as dimethyl sulfoxide and cyclopentane; and nitriles such as acetonitrile. These solvents may be used alone or in combination of two or more.

[0199] The non-aqueous electrolyte secondary battery of the present disclosure preferably includes a separator. Examples of the separator include polyethylene non-woven fabric, polypropylene non-woven fabric, polyamide non-woven fabric, and non-woven fabrics subjected to a hydrophilic treatment, but are not particularly limited thereto.

[0200] The structure of the nonaqueous electrolyte secondary battery disclosed in the present invention is not particularly limited, and generally includes a positive electrode and a negative electrode, and a separator provided as required, and can be made into various shapes corresponding to the purpose of use, such as paper type, cylindrical type, button type, and stacked type.

[0201] Example

[0202] The present invention is described in more detail below by way of examples. The present invention is not limited to the following examples unless it exceeds the gist thereof. In addition, "parts" and "%" represent "parts by mass" and "mass %" unless otherwise specified.

[0203] <Measurement of Bundled CNTs in Dispersion>

[0204] The values ​​of the number % of bundled CNTs, average outer diameter, average fiber length, and average aspect ratio in the carbon nanotube dispersion of Examples were determined by SEM image analysis according to the method described in the above section <Bundled Carbon Nanotubes>.

[0205] <Measurement of average diameter of raw material CNT>

[0206] The average diameter of the carbon nanotubes used as a raw material was determined by TEM image analysis according to the method described in the above-mentioned [Raw material carbon nanotubes].

[0207] <Manufacturing of Bundle-Shaped CNT>

[0208] [Production Example of Raw Material CNT (A)]

[0209] By the method described in paragraph

[0117] of Japanese Patent Laid-Open No. 2018-150218, a CNT synthesis catalyst is prepared. Thereafter, a quartz glass heat-resistant plate with 1.5g of the CNT synthesis catalyst is arranged in the central part of a horizontal reaction tube with a volume of 10L that can be pressurized and can be heated by an external heater. While injecting nitrogen gas, exhaust is performed, and the air in the reaction tube is replaced by nitrogen gas, and the environment in the horizontal reaction tube is set to an oxygen concentration of less than 1% by volume. Then, an external heater is used to heat until the center temperature in the horizontal reaction tube becomes 680°C. After reaching 680°C, propane gas is introduced into the reaction tube at a flow rate of 2L per minute as a carbon source, and a contact reaction is performed for 2 hours. After the reaction is completed, the gas in the reaction tube is replaced by nitrogen gas, and the temperature of the reaction tube is cooled to less than 100°C and taken out, thereby obtaining CNT (A). The average diameter of CNT (A) is 9.1nm.

[0210] [Production Example (1)]

[0211] 100 parts of 8S (carbon nanotubes from JEIO, with an average diameter of 6.8 nm) as a carbon source and 9900 parts of ethanol as a treatment solvent were mixed, wet mixed using Filmix (manufactured by PRIMIX), and then dried by heating at 65°C to remove the solvent to prepare a precursor (1). Next, the precursor (1) was filled in a graphite crucible, and heated in a calcining furnace under an argon atmosphere at a heating rate of 10°C / min until the temperature in the furnace reached 1700°C, and then heat treated at 1700°C for 2 hours to obtain CNT (1).

[0212] [Production Example (2) to Production Example (6)]

[0213] CNTs (2) to (6) were obtained by the same method as in Production Example (1) except that the raw material carbon nanotubes, treatment solvent, additives, and calcination conditions were changed to those shown in Table 1.

[0214] [Production Example (7)]

[0215] 100 parts of 8S (carbon nanotubes from JEIO, with an average diameter of 6.8 nm) as a carbon source and 9900 parts of a mixed solvent (a solvent in which toluene and n-propanol are mixed at a mass ratio of 1:1) as a treatment solvent are mixed, wet-mixed using ultrasonic waves, and then dried by heating at 65°C to remove the solvent to prepare a precursor (7). Next, the precursor (7) is filled in a graphite crucible, and heated in a calcining furnace under an argon atmosphere at a heating rate of 10°C / min until the temperature in the furnace reaches 1700°C, and then heat-treated at 1700°C for 2 hours to obtain CNT (7).

[0216] [Table 1]

[0217] Table 1

[0218] Manufacturing example Raw material CNT Average diameter Mass Handling solvents additive Mass Mass Calcination conditions Processing CNT (1) 8S 6.8nm 100 EA - - 9900 1700℃-2 hours CNT(1) (2) 8S 6.8nm 95 EA Boric acid 8 9900 1700℃-2 hours CNT(2) (3) 8S 6.8nm 95 NPA - - 9900 1700℃-2 hours CNT(3) (4) 8S 6.8nm 95 W Boric acid 8 9900 1700℃-2 hours CNT(4) (5) CNT(A) 9.1nm 95 EA Boric acid - 9900 1700℃-2 hours CNT(5) (6) 100P 13.7nm 95 EA Boric acid 5 9900 1700℃-1 hour CNT(6) (7) 8S 6.8nm 95 TOL / NPA Boric acid 8 9900 1700℃-2 hours CNT(7)

[0219] 8S: Carbon nanotubes (JENOTUBE) from JEIO

[0220] EA: Ethanol

[0221] NPA: n-propanol

[0222] W: Water

[0223] 100P: Carbon nanotubes from Kumho Petrochemical

[0224] TOL / NPA: a mixed solution of toluene and n-propanol in a mass ratio of 1:1

[0225] <Production of CNT dispersion>

[0226] [Example 1] CNT dispersion (W1)

[0227] 97.7 parts of ion exchange water, 0.45 parts of dispersant (1) (polyvinyl pyrrolidone (manufactured by Nippon Catalyst Co., Ltd., K-30)), and 0.05 parts of defoamer (A) (SN-Defoamer 1312 manufactured by San-nopco Co., Ltd.) were added to a stainless steel container, and stirred with a disperser until it became uniform. Thereafter, 1.8 parts of treated CNT (1) were added while stirring with a disperser, and further stirred with a disperser until it became uniform. Then, a high-pressure homogenizer (manufactured by SUGINO Machine Co., Ltd., Starburst 10) was used for dispersion treatment. The dispersion treatment was performed using a single nozzle chamber, with a nozzle diameter of 0.17 mm and a pressure of 100 MPa, and 6 passes were performed to obtain a CNT dispersion (W1).

[0228] [Example 3, Example 6, Example 7, Example 9, Example 10] CNT dispersion (W3, W6, W7, W9, W10)

[0229] CNT dispersion (W3), CNT dispersion (W6), CNT dispersion (W7), CNT dispersion (W9), and CNT dispersion (W10) were obtained by the same method as Example 1, except that the type of treated CNT, the amount of CNT added, the amount of ion exchange water added, the type of dispersant, the amount of dispersant added, the amount of defoaming agent added, and the number of passes were changed as shown in Table 2.

[0230] [Example 4] CNT dispersion (W4)

[0231] 92.27 parts of ion exchange water, 3.2 parts of dispersant (4) (polyacrylic acid (manufactured by Toagosei Co., Ltd., Jurymer AC-10LP)), 0.48 parts of sodium carbonate (Na2CO3), and 0.05 parts of defoamer (A) (SN-Defoamer 1312 manufactured by San-nopco Co., Ltd.) were added to a stainless steel container, and stirred with a disperser until it becomes uniform. Thereafter, 4 parts of treated CNT (2) were added while stirring with a disperser, and further stirred with a disperser until it becomes uniform. Then, a high-pressure homogenizer (manufactured by SUGINO Machine Co., Ltd., Starburst 10) was used for dispersion treatment. The dispersion treatment was performed using a single nozzle chamber, with a nozzle diameter of 0.17 mm and a pressure of 100 MPa, and the CNT dispersion (W4) was obtained by passing the treatment four times.

[0232] [Example 2] CNT dispersion (W2)

[0233] In a glass bottle, 2 parts of treated CNT (1), 0.5 parts of dispersant (7), 0.05 parts of defoamer (A) (SN-Defoamer 1312 manufactured by San-nopco Co., Ltd.), 97.45 parts of ion exchange water and 140 parts of zirconia beads (bead diameter 0.3 mmφ) were placed, and a paint conditioner manufactured by Red Devil Co., Ltd. was used to perform a dispersion treatment for 4 hours, after which the zirconia beads were separated to obtain a CNT dispersion (W2).

[0234] [Example 5, Example 8, Example 16] CNT dispersion (W5), CNT dispersion (W8), CNT dispersion (W19)

[0235] CNT dispersion (W5), CNT dispersion (W8) and CNT dispersion (W19) were obtained by the same method as in Example 2, except for changing the type of treated CNT, the amount of CNT added, the amount of ion exchange water added, the type of dispersant, the amount of dispersant added, the amount of defoaming agent added and the dispersion time recorded in Table 2.

[0236] [Example 11] CNT dispersion (W14)

[0237] 96.44 parts of ion exchange water, 2.1 parts of dispersant (4) (polyacrylic acid (manufactured by Toagosei Co., Ltd., Jurymer AC-10LP)), 0.21 parts of sodium carbonate, and 0.05 parts of defoamer (A) (SN-Defoamer 1312 manufactured by San-nopco Co., Ltd.) were added to a stainless steel container, and stirred with a disperser until the mixture became uniform. Thereafter, 1.2 parts of treated CNT (1) were added while stirring with a disperser, and further stirred with a disperser until the mixture became uniform. Then, a high-pressure homogenizer (manufactured by SUGINO Machine Co., Ltd., Starburst 10) was used for dispersion treatment. The dispersion treatment was performed using a single nozzle chamber with a nozzle diameter of 0.17 mm and a pressure of 100 MPa for 5 passes. The obtained dispersion was subjected to a centrifugal separation device to remove the precipitate. Furthermore, 80 parts of the stirring liquid and 120 parts of zirconia beads (bead diameter 1 mmφ) were placed in a glass bottle and the dispersion treatment was performed for 5 hours using a paint conditioner manufactured by Red Devil. The zirconia beads were then separated to obtain a CNT dispersion (W14).

[0238] [Example 12] CNT dispersion (W15)

[0239] A CNT dispersion (W15) was obtained by the same method as in Example 11, except that the type of treated CNTs, the amount of CNTs added, the amount of ion exchange water added, the type of dispersant, the amount of dispersant added, the type of alkaline compound, the amount of alkaline compound added, the amount of defoaming agent added, and the dispersion time were changed to those described in Table 2.

[0240] [Example 13] CNT dispersion (W16)

[0241] A CNT dispersion (W16) was obtained by the same method as in Example 11, except that the type of treated CNTs, the amount of CNTs added, the amount of ion exchange water added, the type of dispersant, the amount of dispersant added, the amount of defoaming agent added, and the dispersion time were changed to those described in Table 2, and no alkaline compound was used.

[0242] [Example 14] CNT dispersion (W17)

[0243] 97.95 parts of ion exchange water, 0.5 parts of dispersant (2) (sodium carboxymethyl cellulose (manufactured by Nippon Paper Industries, Ltd., APP-084)), and 0.05 parts of defoamer (A) (SN-Defoamer 1312 manufactured by San-nopco Co., Ltd.) were added to a stainless steel container, and stirred with a disperser until it became uniform. Thereafter, 1.2 parts of CNT (1) and 0.3 parts of CNT (8) (manufactured by Hamamatsu Carbonics, NFT005) were added while stirring with a disperser, and further stirred with a disperser until it became uniform. Then, a high-pressure homogenizer (manufactured by SUGINO Machine, Starburst 10) was used for dispersion treatment. The dispersion treatment was carried out using a single nozzle chamber with a nozzle diameter of 0.17 mm and a pressure of 100 MPa for 20 passes. The obtained dispersion was subjected to a centrifugal separation device to remove the precipitate. Furthermore, 80 parts of the stirring liquid and 120 parts of zirconia beads (bead diameter 1 mmφ) were placed in a glass bottle and the dispersion treatment was carried out for 10 hours using a paint conditioner manufactured by Red Devil. The zirconia beads were then separated to obtain a CNT dispersion (W17).

[0244] [Example 15] CNT dispersion (W18)

[0245] 97.95 parts of ion exchange water, 0.5 parts of dispersant (2) (sodium carboxymethyl cellulose (manufactured by Nippon Paper Industries, Ltd., APP-084)), and 0.05 parts of defoamer (A) (SN-Defoamer 1312 manufactured by San-nopco Co., Ltd.) were added to a stainless steel container, and stirred with a disperser until it became uniform. Thereafter, 1.35 parts of CNT (1) and 0.15 parts of CNT (8) (NFT005 manufactured by Hamamatsu Carbonics Co., Ltd.) were added while stirring with a disperser, and further stirred with a disperser until it became uniform. Then, a high-pressure homogenizer (manufactured by SUGINO Machine Co., Ltd., Starburst 10) was used for dispersion treatment. The dispersion treatment was performed using a single nozzle chamber with a nozzle diameter of 0.17 mm and a pressure of 100 MPa, and the obtained dispersion was subjected to 10 passes. The precipitate was removed from the obtained dispersion using a centrifugal separator to obtain a CNT dispersion (W18).

[0246] [Comparative Example 1]

[0247] According to the composition shown in Table 2, 140 parts of treated CNT, ion exchange water, dispersant, defoaming agent and zirconia beads (bead diameter 0.3 mmφ) were placed in a glass bottle, and a paint conditioner manufactured by Red Devil was used for 20 hours of dispersion treatment, after which the zirconia beads were separated to obtain a CNT dispersion (W11).

[0248] [Comparative Example 2]

[0249] According to the composition shown in Table 2, 140 parts of treated CNT, ion exchange water, dispersant, defoaming agent and zirconia beads (bead diameter 0.3 mmφ) were placed in a glass bottle, and a paint conditioner manufactured by Red Devil was used to perform a dispersion treatment for 0.5 hours, after which the zirconia beads were separated to obtain a CNT dispersion liquid (W13).

[0250] The list of the blending compositions is shown in Table 2. In addition, the blending amounts of the treated CNTs, dispersants, and defoaming agents in the table are all values ​​converted to solid content.

[0251] <Evaluation of CNT dispersion>

[0252] The following evaluations were performed using the obtained CNT dispersion. The results are shown in Table 2.

[0253] (Viscosity)

[0254] After the CNT dispersion was allowed to stand in a thermostatic bath at 25°C for more than 1 hour, the CNT dispersion was fully stirred and then immediately measured using a B-type viscometer rotor at a rotation speed of 60 rpm. Regarding the rotor used in the measurement, when the viscosity value was less than 100 mPa·s, a No. 1 rotor was used, when the viscosity value was 100 mPa·s or more and less than 500 mPa·s, a No. 2 rotor was used, when the viscosity value was 500 mPa·s or more and less than 2000 mPa·s, a No. 3 rotor was used, and when the viscosity value was 2000 mPa·s or more and less than 10000 mPa·s, a No. 4 rotor was used.

[0255] [Judgment Criteria]

[0256] ◎: Less than 2000mPa·s (excellent)

[0257] ○: 2000 mPa·s or more and less than 5,000 mPa·s (good)

[0258] △: 5,000mPa·s or more and less than 10,000mPa·s (acceptable)

[0259] ×: 10,000 mPa·s or more, sedimentation or separation (poor)

[0260] (Storage stability)

[0261] The CNT dispersion liquid was left to stand for 7 days at 50° C. before and after storage, and the change in liquid properties (easiness of stirring when stirred with a spatula) was confirmed and evaluated according to the following criteria.

[0262] [Judgment Criteria]

[0263] ○: No increase in viscosity. No problem (good)

[0264] △: Viscosity increased, but no gelation occurred (OK)

[0265] ×: Gelation occurred (extremely bad)

[0266] (Volume resistivity)

[0267] Using an applicator, the CNT dispersion was applied to a polyethylene terephthalate (PET) substrate, and then dried in an oven at 120°C for 30 minutes to obtain a CNT coating (film thickness 3 μm). Thereafter, the surface resistivity (Ω / Υ) of the dried coating was measured using (Nittoseiko Analytech: Loresta GP, MCP-T610). After the measurement, the volume resistivity (Ω·cm) of the coating was calculated by multiplying the thickness of the CNT coating formed on the PET substrate. The thickness of the coating was calculated by subtracting the film thickness of the PET substrate from the average value obtained by measuring 5 points in the film using a film thickness meter. The judgment criteria are shown below.

[0268] [Judgment Criteria]

[0269] ◎: Volume resistivity of CNT coating (Ω·cm) is less than 7×10 -3 (excellent)

[0270] ○: Volume resistivity (Ω·cm) of CNT coating is 7×10 -3 More than and less than 1×10 -2 (good)

[0271] △: Volume resistivity of CNT coating (Ω·cm) is 1×10 -2 More than and less than 2×10 -2 (Can)

[0272] ×: Volume resistivity (Ω·cm) of CNT coating is 2×10 -2 Above (bad)

[0273] (Volume resistivity of negative electrode film)

[0274] First, the obtained CNT dispersion, ion exchange water, and 12.5 parts of a 2% aqueous solution of carboxymethylcellulose (CMC) (manufactured by Daicel Finechem Co., Ltd., #1190) were mixed, and stirred at 2000 rpm for 30 seconds using a rotary mixer to obtain a CNT resin composition. At this time, the amount of the CNT dispersion was adjusted so that the amount of CNT in 100 parts of the composite slurry became 0.27 parts.

[0275] Thereafter, 2.4 parts of silicon monoxide (manufactured by Osaka Titanium Technologies, silicon monoxide (SILICON MONOOXIDE), SiO 1.3C 5μm) were added, and a self-rotation and revolution mixer was used to stir at 2000rpm for 30 seconds. Furthermore, 21.9 parts of artificial graphite (manufactured by Japan Graphite Industry Co., Ltd., CGB-20) were added, and a self-rotation and revolution mixer was used to stir at 2000rpm for 30 seconds. Then, 0.78 parts of styrene butadiene emulsion (manufactured by JSR Co., Ltd., TRD2001) were added, and a self-rotation and revolution mixer was used to stir at 2000rpm for 30 seconds to obtain a composite material slurry for the negative electrode.

[0276] The obtained negative electrode composite material slurry was used to prepare an electrode having a unit area weight of 8 mg / cm 2 The negative electrode was obtained by coating the PET substrate in a manner and then drying it in an electric oven at 120°C for 30 minutes. Thereafter, the surface resistivity (Ω / Υ) of the dried coating film was measured using Loresta GP, MCP-T610 (Nittoseiko Analytech). On the other hand, the thickness of the negative electrode composite layer was calculated by subtracting the film thickness of the PET substrate from the average value obtained by measuring 5 points in the electrode film using a film thickness meter.

[0277] The volume resistivity (Ω·cm) of the negative electrode composite material layer was calculated by multiplying the surface resistivity of the coating film obtained in this way by the thickness of the negative electrode composite material layer, and was evaluated according to the following criteria.

[0278] [Judgment Criteria]

[0279] ◎: The volume resistivity (Ω·cm) of the negative electrode composite material layer is less than 0.12 (excellent)

[0280] ○: The volume resistivity (Ω·cm) of the negative electrode composite material layer is 0.12 or more and less than 0.15 (good)

[0281] △: The volume resistivity (Ω·cm) of the negative electrode composite material layer is 0.15 or more and less than 0.25 (acceptable)

[0282] ×: The volume resistivity (Ω·cm) of the negative electrode composite material layer is 0.25 or more (poor)

[0283] (Peel strength of negative electrode film)

[0284] Use the applicator to make the electrode weight per unit area 8mg / cm 2 The obtained negative electrode composite material slurry is applied on a copper foil in a manner, and then the coating is dried in an oven at 120°C for 30 minutes. Thereafter, the coating direction is used as the major axis and the rectangle of 90mm×20mm is cut into two strips. A tensile testing machine is used in the determination of the peel strength, and the 180-degree peel test method is used for evaluation. Specifically, a double-sided tape with a size of 100mm×30mm is attached to a stainless steel plate, so that the produced battery electrode composite material layer is closely attached to the other side of the double-sided tape, and it is peeled off while being stretched from bottom to top at a certain speed (50mm / minute), and the average value of the stress at this time is used as the peel strength. The judgment criteria are shown below.

[0285] [Judgment Criteria]

[0286] ◎: The peel strength (N / cm) of the negative electrode composite material layer is 0.5 or more (excellent)

[0287] ○: The peel strength (N / cm) of the negative electrode composite material layer is 0.4 or more and less than 0.5 (good)

[0288] △: The peel strength (N / cm) of the negative electrode composite material layer is 0.3 or more and less than 0.4 (acceptable)

[0289] ×: The peel strength (N / cm) of the negative electrode composite material layer is less than 0.3 (poor)

[0290] (Cycle Characteristics)

[0291] First, a standard positive electrode (SC) was produced as follows.

[0292] In capacity 150cm 393 parts by mass of positive electrode active material (manufactured by BASF TODA Battery Materials Co., Ltd., HED (registered trademark) NCM-111 1100), 4 parts by mass of acetylene black (manufactured by DENKA Co., Ltd., DENKA BLACK (registered trademark) HS100), and 3 parts by mass of polyvinylidene fluoride (PVDF) (manufactured by Kureha Battery Materials Japan Co., Ltd., Kureha KF polymer W#1300) were added to a plastic container, and then mixed with a spatula until the powder became uniform. Thereafter, 20.5 parts by mass of NMP were added, and a self-rotation / revolution mixer was used to stir at 2000 rpm for 30 seconds. Thereafter, the mixture in the plastic container was mixed with a spatula until it became uniform, and the self-rotation / revolution mixer was used to stir at 2000 rpm for 30 seconds. Then, 14.6 parts by mass of NMP was added, and the mixture was stirred at 2000 rpm for 30 seconds using the rotation / revolution mixer. Finally, a high-speed stirrer was used to stir at 3000 rpm for 10 minutes to obtain a standard positive electrode composite slurry. Thereafter, the standard positive electrode composite slurry was applied to an aluminum foil with a thickness of 20 μm as a current collector using an applicator, and then dried in an electric oven at 120°C for 30 minutes, and the unit area weight per unit area of ​​the electrode was adjusted to 20 mg / cm 2 The composite material layer was then rolled using a roller press to a density of 3.1 g / cm 3 Standard positive electrode (SC).

[0293] Separately, the obtained negative electrode composite material slurry was applied onto a 20 μm thick copper foil as a current collector using an applicator, and then dried in an oven at 80° C. for 30 minutes to obtain an electrode with a unit area weight of 10 mg / cm 2 The negative electrode composite material layer was produced by rolling using a roller press to obtain a density of 1.6 g / cm 3 of the negative electrode.

[0294] The obtained negative electrode and the obtained standard positive electrode were punched into 50 mm × 45 mm and 45 mm × 40 mm, respectively, and inserted into an aluminum laminate bag with a separator (porous polypropylene film) inserted therebetween, and dried in an electric oven at 70 ° C for 1 hour. Then, in a glove box filled with argon gas, 2 mL of electrolyte was injected, and the aluminum laminate bag was sealed to prepare a non-aqueous electrolyte secondary battery.

[0295] The electrolyte is a non-aqueous electrolyte prepared by dissolving LiPF6 at a concentration of 1M in a mixed solvent of ethylene carbonate, dimethyl carbonate, and diethyl carbonate in a ratio of 1:1:1 (volume ratio), and then adding 1 part of vinylene carbonate (VC) as an additive relative to 100 parts of the electrolyte.

[0296] The obtained non-aqueous electrolyte secondary battery was placed in a constant temperature room at 40°C, and a charge and discharge device (manufactured by Hokuto Electric Co., Ltd., SM-8) was used for charge and discharge measurement. After constant current and constant voltage charging (cut-off current 2.5mA (0.05C)) at a charge end voltage of 4.3V at a charging current of 25mA (0.5C), constant current discharge was performed at a discharge current of 25mA (0.5C) with a discharge end voltage of 3V. The operation was repeated 200 times. The cycle characteristics can be expressed by the following formula 2 as the ratio of the 3rd 0.5C discharge capacity to the 200th 0.5C discharge capacity at 25°C.

[0297] The judgment criteria are shown below.

[0298] (Formula 2)

[0299] Cycle characteristics = 200th 0.5C discharge capacity / 3rd 0.5C discharge capacity × 100 (%)

[0300] [Judgment Criteria]

[0301] ◎◎: Cycle performance is 85% or more (best)

[0302] ◎: Cycle characteristics are 80% or more and less than 85% (extremely good)

[0303] ○: Cycle characteristics are 70% or more and less than 80% (excellent)

[0304] ○△: Cycle characteristics are 60% or more and less than 70% (good)

[0305] △: Cycle performance is 50% or more and less than 60% (acceptable)

[0306] ×: Cycle characteristics less than 50% (poor)

[0307] (Change rate of film thickness before and after cycle)

[0308] The battery (cell) before and after evaluation of the cycle characteristics were disassembled, and the change rate of the thickness of the composite material layer was calculated from cross-sectional observation using SEM, and evaluated according to the following criteria.

[0309] S: The change rate of the thickness of the negative electrode composite material layer (%) is less than 8%

[0310] A: The change rate (%) of the thickness of the negative electrode composite material layer is 8% or more and less than 10%

[0311] B: The change rate (%) of the thickness of the negative electrode composite material layer is 10% or more and less than 12%

[0312] C: The change rate of the thickness of the negative electrode composite material layer (%) is 12% or more

[0313] [Table 2]

[0314]

[0315] The abbreviations in Table 2 are shown below.

[0316] Dispersant (1): Polyvinyl pyrrolidone (manufactured by Nippon Catalyst Co., Ltd., K-30)

[0317] Dispersant (2): Carboxymethylcellulose sodium salt (manufactured by Nippon Paper Industries, Ltd., APP-084)

[0318] Dispersant (3): Carboxymethylcellulose ammonium salt (manufactured by Shin-Etsu Industries, Ltd., Metolose (registered trademark) SM-4)

[0319] Dispersant (4): Polyacrylic acid (manufactured by Toa Gosei Co., Ltd., Jurymer AC-10LP)

[0320] Dispersant (5): Carboxymethylcellulose sodium salt (manufactured by Nippon Paper Industries, Ltd., Sunrose (registered trademark) F01MC)

[0321] Defoamer (A): SN-Defoamer 1312 manufactured by San-nopco Co., Ltd.

[0322] According to Table 2, the electrode using the carbon nanotube dispersion of the present disclosure, which includes bundled carbon nanotubes having an average diameter of 3 nm to 30 nm and having a predetermined outer diameter and fiber length, has excellent cycle characteristics. It is speculated that the carbon nanotube dispersion of the present disclosure maintains the coating shape and suppresses degradation by including a predetermined amount of predetermined bundled carbon nanotubes, thereby showing good cycle characteristics.

[0323] On the other hand, in Comparative Examples 1 and 2, the dispersibility or conductivity of the carbon nanotubes in the dispersion was good, but the bundles in the carbon nanotube dispersion were not maintained, and it was difficult to maintain the coating shape, so it was considered that the cycle characteristics were poor. In addition, the carbon nanotube dispersion using carbon nanotubes that were wet-treated with a boron source had better cycle characteristics. It is speculated that the main reason is that the use of a boron source increases the strength of the bundle of bundled carbon nanotubes, improves the dispersibility, and makes it easy to maintain the bundle shape.

[0324] The present disclosure includes the following embodiments.

[0325] (Item 1) A carbon nanotube dispersion comprising bundled carbon nanotubes having an average diameter of 3 nm to 30 nm and a solvent, wherein the carbon nanotube dispersion comprises:

[0326] The proportion of bundled carbon nanotubes (X) having an outer diameter of 50 nm to 5 μm and a fiber length of 1 μm to 100 μm is 0.2% or more based on the number of carbon nanotubes having an outer diameter of 10 nm or more contained in the carbon nanotube dispersion.

[0327] (Item 2) The carbon nanotube dispersion according to Item 1, wherein the bundled carbon nanotubes (X) having an outer diameter of 50 nm to 5 μm and a fiber length of 1 μm to 100 μm have an average aspect ratio of 5 to 100.

[0328] (Item 3) The carbon nanotube dispersion according to Item 1 or 2, wherein the ratio of the number of bundled carbon nanotubes (X) having an outer diameter of 50 nm to 5 μm and a fiber length of 1 μm to 100 μm is 0.2% to 20%.

[0329] (Item 4) A carbon nanotube dispersion according to any one of Items 1 to 3, wherein the proportion of bundled carbon nanotubes (Y) having an outer diameter of at least 10 nm and less than 50 nm and a fiber length of 1 μm to 5 μm is 10% to 60% based on the number of carbon nanotubes having an outer diameter of at least 10 nm and a fiber length of at least 0.2 μm contained in the carbon nanotube dispersion.

[0330] (Item 5) The carbon nanotube dispersion according to Item 4, wherein the proportion of the number of bundled carbon nanotubes (Y) having an outer diameter of 10 nm or more and less than 50 nm and a fiber length of 1 μm to 5 μm is 20% to 35%.

[0331] (Item 6) A carbon nanotube dispersion according to any one of Items 1 to 5, wherein the proportion of bundled carbon nanotubes (Z) having an outer diameter of at least 10 nm and less than 50 nm and a fiber length of at least 0.2 μm and less than 1 μm is 50% to 80% based on the number of carbon nanotubes having an outer diameter of at least 10 nm and a fiber length of at least 0.2 μm and less than 1 μm contained in the carbon nanotube dispersion.

[0332] (Item 7) The carbon nanotube dispersion according to Item 6, wherein the ratio of the number of the bundled carbon nanotubes (Y) to the number of the bundled carbon nanotubes (Z) (ratio of the number of (Y) / ratio of the number of (Z)) is 0.3 to 0.6.

[0333] (Item 8) The carbon nanotube dispersion according to any one of Items 1 to 7, further comprising a dispersant.

[0334] (Item 9) A conductive film which is a coating film of the carbon nanotube dispersion according to any one of Items 1 to 8.

[0335] (Item 10) A carbon nanotube resin composition comprising the carbon nanotube dispersion according to any one of Items 1 to 8 and a binder.

[0336] (Item 11) A composite material slurry comprising the carbon nanotube resin composition according to Item 10 and an active substance.

[0337] (Item 12) An electrode film, which is a coating film of the composite material slurry according to Item 11.

[0338] (Item 13) A nonaqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, and an electrolyte, wherein at least one of the positive electrode or the negative electrode comprises the electrode film according to Item 12.

[0339] The disclosure of the present application is related to the subject matter described in Japanese Patent Application No. 2022-153032 filed in Japan on September 26, 2022, and all the disclosed contents are incorporated by reference in the present application.

Claims

1. A carbon nanotube dispersion, comprising bundled carbon nanotubes having an average diameter of 3 nm to 30 nm and a solvent, wherein the carbon nanotube dispersion comprises: The proportion of bundled carbon nanotubes (X) having an outer diameter of 50 nm to 5 μm and a fiber length of 1 μm to 100 μm is 0.2% or more based on the number of carbon nanotubes having an outer diameter of 10 nm or more contained in the carbon nanotube dispersion. 2 . The carbon nanotube dispersion according to claim 1 , wherein the bundled carbon nanotubes (X) having an outer diameter of 50 nm to 5 μm and a fiber length of 1 μm to 100 μm have an average aspect ratio of 5 to 100. 3 . 3 . The carbon nanotube dispersion according to claim 1 , wherein the ratio of the number of the bundled carbon nanotubes (X) having an outer diameter of 50 nm to 5 μm and a fiber length of 1 μm to 100 μm is 0.2% to 20%.

4. The carbon nanotube dispersion according to claim 1, wherein the proportion of bundled carbon nanotubes (Y) having an outer diameter of 10 nm or more and less than 50 nm and a fiber length of 1 μm to 5 μm is 10% to 60% based on the number of carbon nanotubes having an outer diameter of 10 nm or more and a fiber length of 0.2 μm or more contained in the carbon nanotube dispersion. 5 . The carbon nanotube dispersion according to claim 4 , wherein the proportion of the number of bundled carbon nanotubes (Y) having an outer diameter of 10 nm or more and less than 50 nm and a fiber length of 1 μm to 5 μm is 20% to 35%.

6. A carbon nanotube dispersion according to any one of claims 1 to 5, wherein, based on the number of carbon nanotubes with an outer diameter of greater than 10 nm and a fiber length of greater than 0.2 μm contained in the carbon nanotube dispersion, the proportion of bundled carbon nanotubes (Z) having an outer diameter of greater than 10 nm and less than 50 nm and a fiber length of greater than 0.2 μm and less than 1 μm is 50% to 80%.

7. The carbon nanotube dispersion according to claim 6, wherein the ratio of the number of the bundled carbon nanotubes (Y) to the number of the bundled carbon nanotubes (Z) (ratio of the number of (Y) / ratio of the number of (Z)) is 0.3 to 0.

6. 8 . The carbon nanotube dispersion according to claim 1 , further comprising a dispersant. 9 . A conductive film, which is a coating film of the carbon nanotube dispersion liquid according to claim 1 . 10 . A carbon nanotube resin composition comprising the carbon nanotube dispersion according to claim 1 and a binder. 11 . A composite material slurry comprising the carbon nanotube resin composition according to claim 10 and an active substance.

12. An electrode film, which is a coating film of the composite material slurry according to claim 11. 13 . A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, and an electrolyte, wherein at least one of the positive electrode and the negative electrode comprises the electrode film according to claim 12 .

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery

    JP1992155776A

  • Nonaqueous electrolyte secondary battery

    JP1992237971A

  • Negative electrode material and secondary battery using the same

    JP2004178922A

  • Multilayer carbon nanotube and method for producing multilayer carbon nanotube

    JP2018150218A

  • Conductive material dispersion and lithium secondary battery manufactured using the same

    JP2018534731A